Resin composition
By using a resin composition including a polymer compound, an epoxy resin, a thermally conductive filler and an active ester curing agent, the balance problem of thermal conductivity, adhesion strength and warpage problems of insulating layer are solved, and excellent thermal conductivity, peel strength and warpage suppression effects are achieved.
Patent Information
- Application Number
- CN202210325373.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2017-03-23
- Filing Date
- 2018-03-22
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2038-03-22
AI Technical Summary
When the prior art increases the thermal conductivity filler content to increase the thermal conductivity coefficient of the insulating layer, the adhesion strength to the metal layer becomes worse, and there is a problem of warping when forming the insulating layer, making it difficult to balance these properties.
Using a resin composition containing a polymer compound, an epoxy resin, a thermally conductive filler and an active ester curing agent, the balance effect of thermal conductivity, peel strength and warpage suppression is obtained by optimizing the component ratio and process conditions.
An insulating layer with excellent performance in thermal conductivity, peel strength and warpage suppression is achieved, and the problem of performance trade-offs is solved.
Smart Images

Figure 359646 
Figure BDA0003573231730000371
Abstract
Description
[0001] This application is a divisional application of the Chinese patent application with application number 201810239264.0, application date March 22, 2018, and invention name “Resin Composition”. Technical Field
[0002] The present invention relates to a resin composition and further to a resin sheet, a circuit board, and a semiconductor chip package using the resin composition. Background Art
[0003] In recent years, the miniaturization and high functionality of electronic devices are progressing, and the mounting density of semiconductor elements in printed wiring boards tends to be higher. In conjunction with the high functionality of the mounted semiconductor elements, a technology for effectively diffusing the heat generated by the semiconductor elements is required. In the case of curing a resin composition containing a thermally conductive filler to form an insulating layer, the thermal conductivity of the resulting insulating layer can be improved by increasing the content of the thermally conductive filler in the resin composition. However, if the content of the thermally conductive filler is increased to a degree that exhibits a sufficient thermal conductivity, the resulting insulating layer tends to have poor adhesion to the metal layer used to form wiring.
[0004] For example, Patent Document 1 discloses that an insulating layer obtained by curing a resin composition containing aluminum nitride or silicon nitride is used in a printed wiring board to exhibit thermal diffusivity and diffuse heat while having low surface roughness and good adhesion strength (peel strength) with a conductor layer.
[0005] [Prior art literature]
[0006] [Patent Document]
[0007] Patent document 1: International Publication No. 2014 / 208352. Summary of the invention
[0008] Problems to be solved by the invention
[0009] In recent years, electronic devices have been miniaturized and highly functionalized, and substrates have been thinner and coreless. In addition to thermal diffusivity and adhesion strength (peel strength), materials are also required to suppress warping when forming an insulating layer. There is a trade-off between these properties, and it is very difficult to design a resin that can achieve a balance.
[0010] The present invention is made to solve the above-mentioned problems, and provides a resin composition, a resin sheet, a circuit substrate, and a semiconductor chip package using the resin composition; the resin composition can obtain a cured product that has achieved a balance in terms of thermal conductivity, excellent peel strength to the metal layer, and suppression of the warping amount generated when forming an insulating layer.
[0011] Means to solve problems
[0012] The present inventors have discovered that an insulating layer having excellent thermal conductivity, excellent peel strength with respect to a metal layer (particularly a metal layer formed by plating), and excellent suppression of warping generated when forming the insulating layer can be obtained by containing (A) a polymer compound having one or more structures selected from the group consisting of a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyalkylene structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, and a polycarbonate structure in the molecule, (B) an epoxy resin, (C) a thermally conductive filler, and (D) an active ester curing agent, thereby completing the present invention.
[0013] That is, the present invention includes the following contents:
[0014] [1] A resin composition comprising:
[0015] (A) a polymer compound having one or more structures selected from the group consisting of a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyalkylene structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, and a polycarbonate structure in the molecule,
[0016] (B) Epoxy resin,
[0017] (C) thermally conductive fillers, and
[0018] (D) an active ester curing agent;
[0019] [2] The resin composition according to [1], wherein the peel strength between the cured product obtained by thermally curing the resin composition at 180°C for 30 minutes and further thermally curing the resin composition at 180°C for 60 minutes and the metal layer formed by plating is 0.4 kgf / cm or more;
[0020] [3] The resin composition according to [1] or [2], wherein the content of the component (C) is 85% by mass or more, based on 100% by mass of the nonvolatile component in the resin composition;
[0021] [4] The resin composition according to any one of [1] to [3], wherein the component (C) comprises aluminum oxide;
[0022] [5] The resin composition according to any one of [1] to [4], wherein the component (C) is surface-treated with an aminosilane coupling agent;
[0023] [6] The resin composition according to any one of [1] to [5], wherein the component (C) is surface-treated with N-phenyl-3-aminoalkyltrimethoxysilane;
[0024] [7] The resin composition according to any one of [1] to [6], wherein a cured product obtained by thermally curing the resin composition at 180°C for 90 minutes has a thermal conductivity of 1.5 W / m·K or more and 5.0 W / m·K or less;
[0025] [8] The resin composition of any one of [1] to [7], wherein the component (A) is at least one selected from a resin having a glass transition temperature of 25°C or less and a resin that is liquid at 25°C;
[0026] [9] The resin composition of any one of [1] to [8], wherein the component (A) has a functional group reactive with the component (B);
[0027]
[10] The resin composition according to any one of [1] to [9], wherein the component (A) has one or more functional groups selected from the group consisting of a hydroxyl group, an acid anhydride group, a phenolic hydroxyl group, an epoxy group, an isocyanate group and a urethane group;
[0028]
[11] The resin composition according to any one of [1] to
[10] , wherein the component (A) has an imide structure;
[0029]
[12] The resin composition according to any one of [1] to
[11] , wherein the component (A) has a phenolic hydroxyl group;
[0030]
[13] The resin composition according to any one of [1] to
[12] , wherein the component (A) has a polybutadiene structure and has a phenolic hydroxyl group;
[0031]
[14] The resin composition according to any one of [1] to
[13] , which is a resin composition for an insulating layer of a semiconductor chip package;
[0032]
[15] The resin composition according to any one of [1] to
[14] , which is a resin composition for an insulating layer of a circuit board in which a circuit is formed by a semi-additive process;
[0033]
[16] A resin sheet comprising: a support, and a resin composition layer provided on the support and comprising the resin composition described in any one of [1] to
[15] ;
[0034]
[17] A circuit board comprising an insulating layer formed from a cured product of the resin composition according to any one of [1] to
[15] ;
[0035]
[18] A semiconductor chip package comprising the circuit substrate described in
[17] and a semiconductor chip mounted on the circuit substrate;
[0036]
[19] A semiconductor chip package comprising a semiconductor chip sealed with the resin composition according to any one of [1] to
[15] or the resin sheet according to
[16] .
[0037] Effects of the Invention
[0038] The present invention can provide a resin composition, a resin sheet, a circuit substrate, and a semiconductor chip package using the resin composition; wherein the resin composition can obtain a cured product that has achieved a balance in terms of thermal conductivity, excellent adhesion strength to a metal layer (especially a metal layer formed by plating), and suppression of the amount of warping generated when forming an insulating layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a schematic cross-sectional view showing an example of the semiconductor chip package (Fan-out type WLP) of the present invention. DETAILED DESCRIPTION
[0040] The resin composition, resin sheet, circuit board, and semiconductor chip package of the present invention are described in detail below.
[0041] [Resin composition]
[0042] The resin composition of the present invention contains: (A) a polymer compound having one or more structures selected from the group consisting of a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyalkylene structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, and a polycarbonate structure in the molecule, (B) an epoxy resin, (C) a thermally conductive filler, and (D) an active ester curing agent.
[0043] By making the resin combination contain (A) component, (B) component, (C) component and (D) component, it is possible to obtain an insulating layer excellent in thermal conductivity, peel strength to the metal layer and the suppression of warpage. In addition, the melt viscosity of the aforementioned resin combination can be relatively low. The resin combination can also contain (E) curing agent, (F) curing accelerator, (G) inorganic filler (except the material that meets (C) component) and (H) flame retardant as needed. The following is a detailed description of each component included in the resin combination.
[0044] <(A) A polymer compound having one or more structures selected from the group consisting of a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyalkylene structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, and a polycarbonate structure in the molecule>
[0045] The resin composition contains (A) a polymer compound having one or more structures selected from the group consisting of a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyalkylene structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, and a polycarbonate structure in the molecule. By making the resin composition contain a polymer compound having the above structure, warping of the cured product can be suppressed. It should be noted that "(meth)acrylate" refers to methacrylate and acrylate.
[0046] More specifically, the component (A) preferably has a structure selected from a polybutadiene structure having polybutadiene and hydrogenated polybutadiene, a polysiloxane structure having silica gel, a poly(meth)acrylate structure, a polyalkylene structure (preferably a polyalkylene structure having 2 to 15 carbon atoms, more preferably a polyalkylene structure having 3 to 10 carbon atoms, and further preferably a polyalkylene structure having 5 to 6 carbon atoms), a polyalkyleneoxy structure (preferably a polyalkyleneoxy structure having 2 to 15 carbon atoms, more preferably a polyalkyleneoxy structure having 3 to 10 carbon atoms), The present invention relates to a poly(alkyleneoxy) structure, preferably a poly(alkyleneoxy) structure having 5 to 6 carbon atoms), a polyisoprene structure, a polyisobutylene structure, and a polycarbonate structure, wherein the poly(alkyleneoxy) structure comprises one or more structures selected from the group consisting of a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyisoprene structure, a polyisobutylene structure, and a polycarbonate structure; and more preferably, the poly(alkyleneoxy) structure comprises one or more structures selected from the group consisting of a polybutadiene structure, a polyisoprene structure, and a polycarbonate structure.
[0047] In order to exhibit flexibility, the component (A) preferably has a high molecular weight, and the number average molecular weight (Mn) is preferably 1,000 to 1,000,000, more preferably 5,000 to 900,000. The number average molecular weight (Mn) is a polystyrene-equivalent number average molecular weight measured using GPC (gel permeation chromatography).
[0048] In order to exhibit flexibility, the component (A) is preferably one or more resins selected from the group consisting of a resin having a glass transition temperature (Tg) of 25°C or lower and a resin that is liquid at 25°C.
[0049] The glass transition temperature (Tg) of the resin having a glass transition temperature of 25°C or less is preferably 20°C or less, and more preferably 15°C or less. The lower limit of the glass transition temperature is not particularly limited, and may generally be -15°C or more. In addition, as the resin that is liquid at 25°C, a resin that is liquid at 20°C or less is preferred, and a resin that is liquid at 15°C or less is more preferred.
[0050] The component (A) preferably has a functional group that can react with the component (B) from the viewpoint of improving the mechanical strength of the cured product. The functional group that can react with the component (B) also includes a functional group that is generated by heating.
[0051] In a suitable embodiment, the functional group capable of reacting with component (B) is one or more functional groups selected from the group consisting of hydroxyl, carboxyl, anhydride, phenolic hydroxyl, epoxy, isocyanate and carbamate. Among them, as the functional group, hydroxyl, anhydride, phenolic hydroxyl, epoxy, isocyanate and carbamate are preferred, hydroxyl, anhydride, phenolic hydroxyl and epoxy are more preferred, and phenolic hydroxyl is particularly preferred.
[0052] One suitable embodiment of component (A) is a butadiene resin. As a butadiene resin, a butadiene resin that is liquid at 25°C or has a glass transition temperature of less than 25°C is preferred, and more preferably, one or more resins selected from a resin containing a hydrogenated polybutadiene skeleton, a butadiene resin containing a hydroxyl group, a butadiene resin containing a phenolic hydroxyl group, a butadiene resin containing a carboxyl group, a butadiene resin containing an acid anhydride group, a butadiene resin containing an epoxy group, a butadiene resin containing an isocyanate group, and a butadiene resin containing a carbamate group are preferred, and a butadiene resin containing a phenolic hydroxyl group is further preferred. As a resin containing a hydrogenated polybutadiene skeleton, for example, an epoxy resin containing a hydrogenated polybutadiene skeleton can be cited. As a butadiene resin containing a phenolic hydroxyl group, a resin having a polybutadiene structure and having a phenolic hydroxyl group can be cited.
[0053] Here, "butadiene resin" refers to a resin containing a polybutadiene structure, in which the polybutadiene structure may be contained in the main chain or in the side chain. The butadiene structure may be partially or completely hydrogenated. Here, "resin containing a hydrogenated polybutadiene skeleton" refers to a resin in which at least a part of the polybutadiene skeleton is hydrogenated, and it is not necessarily a resin in which the polybutadiene skeleton is completely hydrogenated.
[0054] The number average molecular weight (Mn) of the butadiene resin is preferably 1,000 to 100,000, more preferably 5,000 to 50,000, more preferably 7,500 to 30,000, and still more preferably 10,000 to 15,000. Here, the number average molecular weight (Mn) of the resin is a polystyrene-equivalent number average molecular weight measured by GPC (gel permeation chromatography).
[0055] When the butadiene resin has a functional group, the functional group equivalent is preferably 100 to 10000, more preferably 200 to 5000. It should be noted that the functional group equivalent refers to the number of grams of the resin containing 1 gram equivalent of the functional group. For example, the epoxy group equivalent can be measured in accordance with JIS K7236. The hydroxyl group equivalent can be calculated by dividing the molecular weight of KOH by the hydroxyl value measured in accordance with JIS K1557-1.
[0056] Specific examples of the butadiene resin include "Ricon 657" (epoxy-containing polybutadiene) manufactured by Cray Valley, "Ricon 130MA8", "Ricon 130MA13", "Ricon 130MA20", "Ricon 131MA5", "Ricon 131MA10", "Ricon 131MA17", "Ricon 131MA20", "Ricon 184MA6" (polybutadiene containing anhydride groups), "JP-100" and "JP-200" (epoxidized polybutadiene) manufactured by Nippon Soda Co., Ltd., "GQ-1000" (polybutadiene introduced with hydroxyl groups and carboxyl groups), "G-1000", "G-2000" and "G-3000" (polybutadiene containing hydroxyl groups at both ends), "GI-1000", "GI-2000" and "GI-3000" (polybutadiene containing hydroxyl groups at both ends), "PB3600" and "PB4700" (polybutadiene skeleton epoxy compounds) manufactured by Daicel Co., Ltd., "EPOFRIEND A1005", "EPOFRIEND A1010" and "EPOFRIEND A1020" (epoxy compounds of styrene-butadiene-styrene block copolymers), Nagase “FCA-061L” (hydrogenated polybutadiene skeleton epoxy compound) and “R-45EPT” (polybutadiene skeleton epoxy compound) manufactured by ChemteX Corporation, etc.
[0057] In addition, as another suitable embodiment of component (A), a resin having an imide structure may also be used. As the resin having an imide structure, a linear polyimide (polyimide described in Japanese Unexamined Patent Publication No. 2006-37083 and International Publication No. 2008 / 153208) using hydroxyl-terminated polybutadiene, a diisocyanate compound and a tetrabasic acid anhydride as raw materials may be cited. The content of the polybutadiene structure of the polyimide resin is preferably 60% to 95% by mass, more preferably 75% to 85% by mass. The details of the polyimide resin may be referred to the records of Japanese Unexamined Patent Publication No. 2006-37083 and International Publication No. 2008 / 153208, and the contents thereof are introduced into this specification.
[0058] One suitable embodiment of component (A) is isoprene resin. Specific examples of isoprene resin include "KL-610" and "KL-613" manufactured by Kuraray Co., Ltd. Here, "isoprene resin" refers to a resin containing a polyisoprene structure, and the polyisoprene structure in these resins may be contained in the main chain or in the side chain.
[0059] In addition, a suitable embodiment of component (A) is a carbonate resin. As the carbonate resin, a carbonate resin with a glass transition temperature of less than 25°C is preferred, and it is preferably selected from one or more of a carbonate resin containing a hydroxyl group, a carbonate resin containing a phenolic hydroxyl group, a carbonate resin containing a carboxyl group, a carbonate resin containing anhydride groups, a carbonate resin containing an epoxy group, a carbonate resin containing an isocyanate group, and a carbonate resin containing a carbamate group. Here, "carbonate resin" refers to a resin containing a polycarbonate structure, and the polycarbonate structure in these resins can be contained in the main chain or in the side chain.
[0060] The number average molecular weight (Mn) of the carbonate resin and the functional group equivalent when having a functional group are the same as those of the butadiene resin, and the preferred ranges are also the same.
[0061] Specific examples of the carbonate resin include "T6002" and "T6001" (polycarbonate diol) manufactured by Asahi Kasei Chemicals Corporation, and "C-1090", "C-2090", and "C-3090" (polycarbonate diol) manufactured by Kuraray Co., Ltd.
[0062] In addition, a linear polyimide with a hydroxyl-terminated polycarbonate, a diisocyanate compound, and a tetrabasic acid anhydride as raw materials can also be used. The content of the polycarbonate structure of the polyimide resin is preferably 60% to 95% by mass, more preferably 75% to 85% by mass. The details of the polyimide resin can be referred to the record of International Publication No. 2016 / 129541, and its content is introduced into this specification.
[0063] Another suitable embodiment of component (A) is an acrylic resin. As the acrylic resin, an acrylic resin having a glass transition temperature (Tg) of 25°C or less is preferred, and more preferably, one or more resins selected from acrylic resins containing hydroxyl groups, acrylic resins containing phenolic hydroxyl groups, acrylic resins containing carboxyl groups, acrylic resins containing acid anhydride groups, acrylic resins containing epoxy groups, acrylic resins containing isocyanate groups, and acrylic resins containing carbamate groups. Here, "acrylic resin" refers to a resin containing a poly (meth) acrylate structure, and the poly (meth) acrylate structure in these resins may be contained in the main chain or in the side chain.
[0064] The number average molecular weight (Mn) of the acrylic resin is preferably 10000 to 1000000, more preferably 30000 to 900000. Here, the number average molecular weight (Mn) of the resin is a polystyrene-equivalent number average molecular weight measured using GPC (gel permeation chromatography).
[0065] When the acrylic resin has a functional group, the functional group equivalent is preferably 1,000 to 50,000, more preferably 2,500 to 30,000.
[0066] Specific examples of acrylic resins include: TEISANRESIN "SG-70L", "SG-708-6", "WS-023", "SG-700AS", "SG-280TEA" (carboxyl-containing acrylic copolymer resin, acid value 5 to 34 mgKOH / g, weight average molecular weight 400,000 to 900,000, Tg-30 to 5°C), "SG-80H", "SG-80H-3", "SG-P3" (epoxy-containing acrylic copolymer resin, epoxy equivalent 4761 to 14285 g / eq, weight average molecular weight 350,000) manufactured by Nagase ChemteX Co., Ltd. ~850,000, Tg11~12℃), "SG-600TEA", "SG-790" (hydroxyl-containing acrylate copolymer resin, hydroxyl value 20~40mgKOH / g, weight average molecular weight 500,000~1.2 million, Tg-37~-32℃), "ME-2000", "W-116.3" (carboxyl-containing acrylate copolymer resin), "W-197C" (hydroxyl-containing acrylate copolymer resin), "KG-25", "KG-3000" (epoxy-containing acrylate copolymer resin) manufactured by Negami Industries, Ltd., etc.
[0067] Furthermore, another preferred embodiment of the component (A) is a siloxane resin, an alkylene resin, an alkyleneoxy resin, or an isobutylene resin.
[0068] Specific examples of siloxane resins include "SMP-2006", "SMP-2003PGMEA", "SMP-5005PGMEA" manufactured by Shin-Etsu Silicone Co., Ltd., and linear polyimide (International Publication No. 2010 / 053185) using amino-terminated polysiloxane and tetrabasic acid anhydride as raw materials. Here, "siloxane resin" refers to a resin containing a polysiloxane structure, and the polysiloxane structure in these resins may be contained in the main chain or in the side chain.
[0069] Specific examples of alkylene resins and alkyleneoxy resins include "PTXG-1000" and "PTXG-1800" manufactured by Asahi Kasei Fibers Corporation, "YX-7180" (a resin containing an alkylene structure having an ether bond) manufactured by Mitsubishi Chemical Corporation, and the like. "EXA-4850-150", "EXA-4816" and "EXA-4822" manufactured by DIC Corporation, "EP-4000", "EP-4003", "EP-4010" and "EP-4011" manufactured by ADEKA Corporation, "BEO-60E" and "BPO-20E" manufactured by Shin Nippon Chemical Co., Ltd., and "YL7175" and "YL7410" manufactured by Mitsubishi Chemical Corporation, and the like. Here, "alkylene resin" refers to a resin containing a polyalkylene structure, and "alkyleneoxy resin" refers to a resin containing a polyalkyleneoxy structure. In these resins, the polyalkylene structure and the polyalkyleneoxy structure may be contained in the main chain or in the side chain.
[0070] Specific examples of isobutylene resins include "SIBSTAR-073T" (styrene-isobutylene-styrene triblock copolymer) and "SIBSTAR-042D" (styrene-isobutylene diblock copolymer) manufactured by Kaneka Corporation. Here, "isobutylene resin" refers to a resin containing a polyisobutylene structure, and the polyisobutylene structure in these resins may be contained in the main chain or in the side chain.
[0071] In addition, as further suitable embodiments of the component (A), there can be cited acrylic rubber particles, polyamide microparticles, silicone particles, etc. Specific examples of acrylic rubber particles include microparticles of a resin that is insoluble and infusible in an organic solvent by chemically crosslinking a resin that exhibits rubber elasticity, such as acrylonitrile butadiene rubber (nitrile rubber), butadiene rubber, and acrylic rubber, and specifically, XER-91 (manufactured by Japan Synthetic Rubber Co., Ltd.), STAPHYLOID AC3355, AC3816, AC3832, AC4030, AC3364, IM101 (manufactured by Gantsu Kasei Co., Ltd.), PARALOID EXL2655, EXL2602 (manufactured by Kureha Chemical Industry Co., Ltd.), etc. Specific examples of polyamide fine particles include any polyamide fine particles as long as they have a flexible skeleton such as aliphatic polyamide such as nylon or polyamide-imide, and specific examples thereof include VESTOSINT 2070 (manufactured by Daicel-Huels) and SP500 (manufactured by Toray Industries, Ltd.).
[0072] From the viewpoint of imparting flexibility, when the non-volatile component (resin component) of the resin composition except (C) component and (G) component is set to 100 mass %, the content of (A) component in the resin composition is preferably below 65 mass %, more preferably below 60 mass %, and then preferably below 55 mass %, and then more preferably below 50 mass %. In addition, the lower limit is preferably above 10 mass %, more preferably above 15 mass %, and then preferably above 20 mass %, and then more preferably above 25 mass %.
[0073] <(B) Epoxy resin>
[0074] The resin composition of the present invention contains an epoxy resin as component (B). From the viewpoint of further improving the effect of the present invention, component (B) is preferably an epoxy resin having an aromatic structure. The aromatic structure is a chemical structure generally defined as an aromatic structure, and also includes polycyclic aromatics and aromatic heterocycles.
[0075] Examples of the epoxy resin include bixylenol epoxy resins, bisphenol A epoxy resins, bisphenol F epoxy resins, bisphenol S epoxy resins, bisphenol AF epoxy resins, dicyclopentadiene epoxy resins, trisphenol epoxy resins, naphthol novolac epoxy resins, phenol novolac epoxy resins, tert-butyl-catechol epoxy resins, naphthalene epoxy resins, naphthol epoxy resins, anthracene epoxy resins, glycidylamine epoxy resins having an aromatic structure, glycidylester epoxy resins having an aromatic structure, cresol novolac epoxy resins, and the like. The epoxy resins used herein include butadiene epoxy resins, alicyclic epoxy resins, heterocyclic epoxy resins, spiro-ring-containing epoxy resins, cyclohexanedimethanol epoxy resins, naphthylene ether epoxy resins, trimethylol epoxy resins, tetraphenylethane epoxy resins, and aminophenol epoxy resins. The epoxy resins may be used alone or in combination of two or more. Component (B) is preferably one or more selected from bisphenol A epoxy resins, bisphenol F epoxy resins, aminophenol epoxy resins, and naphthalene epoxy resins.
[0076] The epoxy resin preferably contains an epoxy resin having two or more epoxy groups in one molecule. When the non-volatile component of the epoxy resin is set to 100% by mass, it is preferred that at least 50% by mass or more is an epoxy resin having two or more epoxy groups in one molecule. Among them, it is preferred to contain an epoxy resin having two or more epoxy groups in one molecule and being liquid at a temperature of 20°C (hereinafter referred to as "liquid epoxy resin"), and an epoxy resin having three or more epoxy groups in one molecule and being solid at a temperature of 20°C (hereinafter referred to as "solid epoxy resin".). As an epoxy resin, by using a liquid epoxy resin and a solid epoxy resin in combination, a resin composition with excellent flexibility can be obtained. In addition, the fracture strength of the cured product of the resin composition is also improved.
[0077] As the liquid epoxy resin, preferred are bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin having an aromatic structure, glycidyl amine type epoxy resin having an aromatic structure, phenol novolac type epoxy resin, alicyclic epoxy resin having an ester skeleton having an aromatic structure, cyclohexanedimethanol type epoxy resin having an aromatic structure, aminophenol type epoxy resin and epoxy resin having a butadiene structure having an aromatic structure; more preferred are bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, aminophenol type epoxy resin and naphthalene type epoxy resin; further preferred are bisphenol A type epoxy resin, bisphenol F type epoxy resin and aminophenol type epoxy resin. Specific examples of liquid epoxy resins include "HP4032", "HP4032D", and "HP4032SS" (naphthalene-type epoxy resins) manufactured by DIC Corporation, "828US", "jER828EL" (bisphenol A-type epoxy resins), "jER806", and "jER807" (bisphenol F-type epoxy resins), "jER152" (phenol novolac-type epoxy resins), "630" (aminophenol-type epoxy resins), and "630LSD" (glycidylamine-type epoxy resins), "ZX1059" (a mixture of bisphenol A-type epoxy resins and bisphenol F-type epoxy resins) manufactured by Nippon Steel & Sumitomo Metal Chemicals, and Nagase "EX-721" (glycidyl ester type epoxy resin) manufactured by ChemteX, "CELLOXIDE2021P" (alicyclic epoxy resin having an ester skeleton) manufactured by Daicel, "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane) manufactured by Nippon Steel Chemical, and "YX7400" (high resilience epoxy resin) manufactured by Mitsubishi Chemical. These may be used alone or in combination of two or more.
[0078] As solid epoxy resins, preferred are biphenyl type epoxy resins, naphthalene type tetrafunctional epoxy resins, cresol novolac type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol type epoxy resins, biphenyl type epoxy resins, naphthylene ether type epoxy resins, anthracene type epoxy resins, bisphenol A type epoxy resins, bisphenol AF type epoxy resins, and tetraphenylethane type epoxy resins; more preferred are biphenyl type epoxy resins, naphthalene type tetrafunctional epoxy resins, naphthol type epoxy resins, biphenyl type epoxy resins, and naphthylene ether type epoxy resins; further preferred are biphenyl type epoxy resins, naphthalene type tetrafunctional epoxy resins, naphthylene ether type epoxy resins, and biphenyl type epoxy resins. Specific examples of solid epoxy resins include "HP4032H" (naphthalene-type epoxy resin), "HP-4700", "HP-4710" (naphthalene-type tetrafunctional epoxy resin), "N-690" (cresol novolac-type epoxy resin), "N-695" (cresol novolac-type epoxy resin), "HP-7200", "HP-7200L", "HP-7200HH", "HP-7200H", "HP-7200HHH" (dicyclopentadiene-type epoxy resin), "EXA7311" (HP-7311HH) ... ”, “EXA7311-G3”, “EXA7311-G4”, “EXA7311-G4S”, “HP6000” (naphthylene ether type epoxy resin), “EPPN-502H” (trisphenol type epoxy resin) manufactured by Nippon Kayaku Co., Ltd., “NC7000L” (naphthol phenolic type epoxy resin), “NC3000H”, “NC3000”, “NC3000L”, “NC3100” (biphenyl type epoxy resin), “ESN475V” (naphthol type epoxy resin) manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd. ), "ESN485" (naphthol novolac type epoxy resin), "YX4000H" and "YL6121" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical Corporation, "YX4000HK" (biphenyl type epoxy resin), "YL7760" (bisphenol AF type epoxy resin), "YX8800" (anthracene type epoxy resin), "PG-100" and "CG-500" manufactured by Osaka Gas Chemical Co., Ltd., "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical Corporation, and "jER1010" manufactured by Mitsubishi Chemical Corporation (solid bisphenol A type epoxy resin), "jER1031S" (tetraphenylethane type epoxy resin), "157S70" (bisphenol novolac type epoxy resin), "YX4000HK" (bimethylol type epoxy resin), "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Corporation, "PG-100" and "CG-500" manufactured by Osaka Gas Chemical Co., Ltd., "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical Corporation, "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical Corporation, etc. These may be used alone or in combination of two or more.
[0079] When a liquid epoxy resin and a solid epoxy resin are used together as component (B), the mass ratio of the liquid epoxy resin and the solid epoxy resin (solid epoxy resin: liquid epoxy resin) is preferably in the range of 1:0.1 to 1:15. By making the mass ratio of the liquid epoxy resin and the solid epoxy resin in the above range, the following effects can be obtained: i) when used in the form of a resin sheet, appropriate adhesion can be obtained, ii) when used in the form of a resin sheet, sufficient flexibility can be obtained and the workability is improved, and iii) a cured product with sufficient breaking strength can be obtained. From the viewpoint of the effects of i) to iii) above, the mass ratio of the liquid epoxy resin to the solid epoxy resin (solid epoxy resin: liquid epoxy resin) is more preferably in the range of 1:0.3 to 1:10, and further preferably in the range of 1:0.6 to 1:8.
[0080] From the viewpoint of obtaining an insulating layer showing good mechanical strength and insulation reliability, when the non-volatile component in the resin composition is set to 100% by mass, the content of the epoxy resin in the resin composition is preferably 1% by mass or more, more preferably 2% by mass or more, and further preferably 3% by mass or more. As for the upper limit of the content of the epoxy resin, as long as the effect of the present invention is exerted, it is not particularly limited, and is preferably 10% by mass or less, more preferably 8% by mass or less, and further preferably 6% by mass or less.
[0081] In addition, from the viewpoint of obtaining an insulating layer showing good mechanical strength and insulation reliability, when the non-volatile components of the resin composition other than the (C) component and the (G) component are set to 100% by mass, the content of the epoxy resin in the resin composition is 20% by mass or more, more preferably 25% by mass or more, and further preferably 30% by mass or more. As for the upper limit of the epoxy resin content, there is no particular limitation as long as the effect of the present invention is exerted, and it is preferably 70% by mass or less, more preferably 60% by mass or less, and further preferably 55% by mass or less.
[0082] The epoxy equivalent of the epoxy resin is preferably 50 to 5000, more preferably 50 to 3000, further preferably 80 to 2000, further more preferably 110 to 1000. Within this range, an insulating layer having a sufficient crosslinking density of the cured product and a small surface roughness can be obtained. It should be noted that the epoxy equivalent can be measured according to JIS K7236 and is the mass of a resin containing 1 equivalent of epoxy groups.
[0083] The weight average molecular weight of the epoxy resin is preferably 100 to 5000, more preferably 250 to 3000, and still more preferably 400 to 1500. Here, the weight average molecular weight of the epoxy resin is a weight average molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC).
[0084] <(C) Thermally conductive filler>
[0085] The resin composition of the present invention contains (C) a thermally conductive filler. Here, in this specification, the thermally conductive filler refers to an inorganic filler having a thermal conductivity of 20 W / m·K or more.
[0086] As for the material of (C) component, as long as the thermal conductivity is within the above range, it is not particularly limited. As the material contained in (C) component, for example, aluminum oxide, aluminum nitride, boron nitride, silicon carbide, etc. can be listed. Among them, aluminum oxide is particularly suitable. (C) component can be used alone or in combination of two or more. In addition, two or more of the same material can be used in combination.
[0087] From the perspective of obtaining an insulating layer having both excellent thermal conductivity and peel strength and improving fillability, the average particle size of the (C) component is preferably 5 μm or less, more preferably 4 μm or less, and further preferably 3 μm or less, preferably 0.1 μm or more, more preferably 1.0 μm or more, and further preferably 1.5 μm or more. The average particle size of the (C) component can be measured by a laser diffraction-scattering method based on Mie scattering theory. Specifically, a laser diffraction scattering particle size distribution measuring device can be used to prepare a particle size distribution of an inorganic filler material on a volume basis, and the median particle size is used as the average particle size, thereby measuring. The sample to be measured can preferably be a sample in which the (C) component is dispersed in water by ultrasound. As a laser diffraction scattering particle size distribution measuring device, "LA-500" manufactured by Horiba, Ltd., "SALD2200" manufactured by Shimadzu Corporation, etc. can be used. Specifically, it can be measured according to the method described in <Measurement of the average particle size of thermally conductive filler> described later.
[0088] From the viewpoint of obtaining an insulating layer excellent in both thermal conductivity and peel strength and improving filling properties, the specific surface area of the component (C) is preferably 0.5 m 2 The specific surface area of the component (C) is preferably 0.5 m 2 / g~10m 2 / g, more preferably 0.5m 2 / g~5m 2 / g. The specific surface area of the (C) component can be measured by the nitrogen BET method (BET nitrogen adsorption method). Specifically, it can be measured using an automatic specific surface area measuring device. As an automatic specific surface area measuring device, "Macsorb HM-1210" manufactured by Mountech can be used. Specifically, it can be measured according to the method described in <Measurement of the specific surface area of the thermally conductive filler> described later.
[0089] From the viewpoint of improving moisture resistance and dispersibility, component (C) may be treated with one or more surface treatment agents selected from the group consisting of aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, silane coupling agents, alkoxysilane compounds, organosilazane compounds, and titanate coupling agents. Commercially available products of the surface treatment agent include, for example, "KBM403" (3-glycidoxypropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., "KBM803" (3-mercaptopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., "KBE903" (3-aminopropyltriethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., "KBM5783" (N-phenyl-3-aminooctyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., "SZ-31" (hexamethyldisilazane) manufactured by Shin-Etsu Chemical Co., Ltd., "KBM103" (phenyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., and "KBM-4803" (long-chain epoxy-type silane coupling agent) manufactured by Shin-Etsu Chemical Co., Ltd. Among them, from the viewpoint of reducing melt viscosity and improving lamination properties, the component (C) is preferably surface-treated with an aminosilane coupling agent, preferably surface-treated with N-phenyl-3-aminoalkyltrimethoxysilane represented by N-phenyl-3-aminopropyltrimethoxysilane and N-phenyl-3-aminooctyltrimethoxysilane, and more preferably surface-treated with N-phenyl-3-aminooctyltrimethoxysilane.
[0090] From the viewpoint of obtaining an insulating layer having both excellent thermal conductivity and peel strength, when the non-volatile component in the resin composition is set to 100% by mass, the content of the component (C) is preferably 85% by mass or more, more preferably 88% by mass or more, and further preferably 89% by mass or more, or 90% by mass or more. The upper limit is preferably 95% by mass or less, more preferably 93% by mass or less, and further preferably 92% by mass or less.
[0091] <(D) Active ester curing agent>
[0092] The resin composition of the present invention includes (D) active ester curing agent. As active ester curing agent, there is no particular limitation, and usually preferably esters of phenol esters, thiophenol esters, N-hydroxylamine esters, heterocyclic hydroxy compounds, etc., have ester groups with more than 2 high reactive activities in 1 molecule. The active ester curing agent is preferably obtained by the condensation reaction of carboxylic acid compounds and / or thiocarboxylic acid compounds with hydroxy compounds and / or thiol compounds. Especially from the viewpoint of improving heat resistance, it is preferably an active ester curing agent that can be obtained by carboxylic acid compounds and hydroxy compounds, and more preferably an active ester curing agent that can be obtained by carboxylic acid compounds and phenol compounds and / or naphthol compounds. As carboxylic acid compounds, for example benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, pyromellitic acid, etc. can be listed. Examples of the phenol compound or naphthol compound include hydroquinone, resorcinol, bisphenol A, bisphenol F, bisphenol S, phenolphthalein, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucinol, pyrogallol, dicyclopentadiene-type diphenol compounds, and phenol novolac. The "dicyclopentadiene-type diphenol compound" herein refers to a diphenol compound obtained by condensing two molecules of phenol on one molecule of dicyclopentadiene.
[0093] Specifically, active ester compounds containing a dicyclopentadiene-type diphenol structure, active ester compounds containing a naphthalene structure, active ester compounds containing acetylated products of phenol novolac resins, and active ester compounds containing benzoylated products of phenol novolac resins are preferred, and active ester compounds containing a naphthalene structure and active ester compounds containing a dicyclopentadiene-type diphenol structure are more preferred. The so-called "dicyclopentadiene-type diphenol structure" refers to a divalent structure formed by phenylene-dicyclopentylene (dicyclopentylene)-phenylene.
[0094] As the active ester compound, the active ester compounds disclosed in Japanese Patent Publication No. 2004-277460 and Japanese Patent Publication No. 2013-40270 can be used, and commercially available active ester compounds can also be used. As commercially available products of active ester curing agents, active ester compounds containing dicyclopentadiene-type diphenol structures can be listed as "EXB9451", "EXB9460", "EXB9460S", "HPC-8000-65T", "HPC-8000H-65TM", "EXB-8000L-65TM" (manufactured by DIC Corporation), active ester compounds containing naphthalene structures can be listed as "EXB9416-70BK" (manufactured by DIC Corporation), and active ester compounds containing acetylated products of phenol novolac resins can be listed as "DC808" (manufactured by Mitsubishi Chemical Corporation) Examples of active ester compounds of benzoylated products of phenol novolac resins include "YLH1026" (manufactured by Mitsubishi Chemical Corporation), examples of active ester curing agents of acetylated products of phenol novolac resins include "DC808" (manufactured by Mitsubishi Chemical Corporation), examples of active ester curing agents of benzoylated products of phenol novolac resins include "YLH1026" (manufactured by Mitsubishi Chemical Corporation), "YLH1030" (manufactured by Mitsubishi Chemical Corporation), "YLH1048" (manufactured by Mitsubishi Chemical Corporation), and "EXB9050L-62M" (an active ester compound containing a phosphorus atom) manufactured by DIC Corporation.
[0095] When the non-volatile component in the resin composition is set to 100 mass %, the content of the component (D) is preferably 5 mass % or less, more preferably 3 mass % or less, and further preferably 2 mass % or less. In addition, the lower limit is not particularly limited, preferably 0.1 mass % or more, more preferably 0.5 mass % or more. By making the content of the component (D) within the above range, the thermal conductivity and peel strength can be improved.
[0096] <(E) Curing agent>
[0097] The resin composition of the present invention may also contain (E) a curing agent in addition to the component (D). However, the component (E) mentioned here does not include the (D) active ester curing agent. As the (E) curing agent, there is no particular limitation as long as it has the function of curing resins such as the component (B), and examples thereof include phenol curing agents, naphthol curing agents, benzoxazine curing agents, cyanate curing agents, and carbodiimide curing agents. The curing agent may be used alone or in combination of two or more. The component (D) is preferably one or more selected from phenol curing agents, naphthol curing agents, and cyanate curing agents, and preferably one or more selected from phenol curing agents.
[0098] As phenolic curing agents and naphthol curing agents, from the viewpoint of heat resistance and water resistance, phenolic curing agents with a novolac structure or naphthol curing agents with a phenolic structure are preferred. In addition, from the viewpoint of adhesion to the wiring layer, nitrogen-containing phenolic curing agents are preferred, and phenolic curing agents containing triazine skeletons are more preferred. Among them, from the viewpoint of highly satisfying heat resistance, water resistance, and adhesion to the wiring layer, phenolic novolac curing agents containing triazine skeletons are preferred.
[0099] Specific examples of phenol-based curing agents and naphthol-based curing agents include "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Chemical Co., Ltd., "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd., "SN170", "SN180", "SN190", "SN475", "SN485", "SN495V", "SN375", and "SN395" manufactured by Nippon Steel and Sumitomo Metal Corporation, "TD-2090", "LA-7052", "LA-7054", "LA-1356", "LA-3018-50P", "EXB-9500", "HPC-9500", "KA-1160", "KA-1163", and "KA-1165" manufactured by DIC Corporation, and "GDP-6115L" and "GDP-6115H" manufactured by Gunyo Chemical Co., Ltd.
[0100] Specific examples of the benzoxazine-based curing agent include "HFB2006M" manufactured by Showa Highpolymer Co., Ltd. and "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd.
[0101] Examples of the cyanate curing agent include bisphenol A dicyanate, polyphenol cyanate, oligo(3-methylene-1,5-phenylene cyanate), 4,4'-methylenebis(2,6-dimethylphenylcyanate), 4,4'-ethylenediphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanatephenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanatephenyl-1-(methylethylene))benzene, bis(4-cyanatephenyl)sulfide, and bifunctional cyanate resins such as bis(4-cyanatephenyl)ether, polyfunctional cyanate resins derived from phenol novolac resins and cresol novolac resins, and prepolymers obtained by partially triazinizing these cyanate resins. Specific examples of cyanate curing agents include "PT30" and "PT60" manufactured by Lonza Japan (both are phenol novolac-type multifunctional cyanate resins), "BA230", and "BA230S75" (prepolymers in which a part or all of bisphenol A dicyanate is triazine-formulated to form a trimer), etc.
[0102] Specific examples of the carbodiimide-based curing agent include "V-03" and "V-07" manufactured by Nisshinbo Chemical Co., Ltd.
[0103] When the resin composition contains component (E), the content of component (E) in the resin composition is not particularly limited, and when the non-volatile component in the resin composition is set to 100% by mass, it is preferably 5% by mass or less, more preferably 3% by mass or less, and further preferably 2% by mass or less. In addition, the lower limit is not particularly limited, and is preferably 0.1% by mass or more, and more preferably 0.5% by mass or more.
[0104] <(F) Curing Accelerator>
[0105] The resin composition of the present invention may contain (F) a curing accelerator. Examples of the curing accelerator include phosphorus curing accelerators, amine curing accelerators, imidazole curing accelerators, guanidine curing accelerators, and metal curing accelerators. Preferably, phosphorus curing accelerators, amine curing accelerators, imidazole curing accelerators, and metal curing accelerators are used. More preferably, amine curing accelerators, imidazole curing accelerators, and metal curing accelerators are used. One curing accelerator may be used alone, or two or more may be used in combination.
[0106] Examples of the phosphorus-based curing accelerator include triphenylphosphine, phosphonium borate compounds, tetraphenylphosphonium tetraphenylborate, n-butylphosphonium tetraphenylborate, tetrabutylphosphonium decanoate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate, and triphenylphosphonium thiocyanate is preferred.
[0107] Examples of the amine-based curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene, and 4-dimethylaminopyridine and 1,8-diazabicyclo(5,4,0)-undecene are preferred.
[0108] Examples of the imidazole curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole trimellitate, 1-cyanoethyl-2-phenylimidazole trimellitate, 2,4-diamino-6-[2′-methylimidazolyl-(1′)]-ethyl-s-triazine, 2,4- Imidazole compounds such as diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, 2-phenylimidazoline, and adducts of imidazole compounds with epoxy resins, preferably 2-ethyl-4-methylimidazole and 1-benzyl-2-phenylimidazole.
[0109] As the imidazole-based curing accelerator, a commercially available item can be used, and examples thereof include "P200-H50" manufactured by Mitsubishi Chemical Corporation.
[0110] Examples of the guanidine-based curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanidine, 1-ethylbiguanidine, 1-n-butylbiguanidine, 1-n-octadecylbiguanidine, 1,1-dimethylbiguanidine, 1,1-diethylbiguanidine, 1-cyclohexylbiguanidine, 1-allylbiguanidine, 1-phenylbiguanidine, and 1-(o-tolyl)biguanidine. Preferred examples include dicyandiamide and 1,5,7-triazabicyclo[4.4.0]dec-5-ene.
[0111] As metal curing accelerators, for example, organic metal complexes or organic metal salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin can be cited. As specific examples of organic metal complexes, organic cobalt complexes such as cobalt acetylacetonate (II), cobalt acetylacetonate (III), organic copper complexes such as copper acetylacetonate (II), organic zinc complexes such as zinc acetylacetonate (II), organic iron complexes such as iron acetylacetonate (III), organic nickel complexes such as nickel acetylacetonate (II), and organic manganese complexes such as manganese acetylacetonate (II) can be cited. As organic metal salts, for example, zinc octoate, tin octoate, zinc naphthenate, cobalt naphthenate, tin stearate, zinc stearate, etc. can be cited.
[0112] When the resin composition contains the component (F), the content of the component (F) in the resin composition is not particularly limited, but is preferably 0.01% by mass to 1% by mass when the nonvolatile component in the resin composition is 100% by mass.
[0113] <(G) Inorganic fillers (excluding materials meeting the requirements of component (C))>
[0114] The resin composition of the present invention may contain (G) inorganic filler. However, the (G) inorganic filler mentioned here does not include materials that meet the requirements of (C) thermal conductive filler. The material of the (G) component is not particularly limited, and examples thereof include silicon dioxide, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, silicon dioxide is particularly preferred. And as silicon dioxide, spherical silicon dioxide is preferred. One inorganic filler may be used alone, or two or more may be used in combination.
[0115] From the viewpoint of improving circuit embedding and obtaining an insulating layer with low surface roughness, the average particle size of the inorganic filler is preferably 5 μm or less, more preferably 2.5 μm or less, further preferably 2.2 μm or less, and more preferably 2 μm or less. The lower limit of the average particle size is not particularly limited, but is preferably 0.01 μm or more, more preferably 0.05 μm or more, and further preferably 0.1 μm or more. The average particle size of the inorganic filler can be measured in the same manner as the (C) component. Commercially available inorganic fillers having the above-mentioned average particle size include, for example, "YC100C", "YA050C", "YA050C-MJE", and "YA010C" manufactured by Admatechs, "UFP-30" manufactured by Denki Kagaku Kogyo Co., Ltd., "Silfil NSS-3N", "Silfil NSS-4N", and "Silfil NSS-5N" manufactured by Tokuyama Co., Ltd., and "SC2500SQ", "SO-C6", "SO-C4", "SO-C2", and "SO-C1" manufactured by Admatechs.
[0116] From the viewpoint of improving moisture resistance and dispersibility, the inorganic filler is preferably treated with one or more surface treatment agents selected from aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, silane coupling agents, alkoxysilane compounds, organosilazane compounds, titanate coupling agents, etc. The commercially available products of the specific surface treatment agents are as described above.
[0117] When the resin composition contains component (G), the content of component (G) in the resin composition is not particularly limited, and when the non-volatile component in the resin composition is set to 100% by mass, it is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and further preferably 1% by mass or more. The upper limit is preferably 5% by mass or less, more preferably 4% by mass or less, and further preferably 3% by mass or less.
[0118] <(H) Flame retardant>
[0119] The resin composition may contain (H) a flame retardant. Examples of the flame retardant include organic phosphorus flame retardants, organic nitrogen-containing phosphorus compounds, nitrogen compounds, organic silicon flame retardants, metal hydroxides, etc. The flame retardant may be used alone or in combination of two or more.
[0120] As the flame retardant, a commercially available item can be used, and examples thereof include "HCA-HQ" manufactured by Sanko Corporation.
[0121] When the resin composition contains a flame retardant, the content of the component (H) is not particularly limited, but is preferably 0.5 to 10% by mass, more preferably 0.5 to 5% by mass, and even more preferably 0.5 to 3% by mass, based on 100% by mass of the nonvolatile component in the resin composition.
[0122] <(I) Optional Additives>
[0123] The resin composition may contain other additives as necessary. Examples of such other additives include organic metal compounds such as organic copper compounds, organic zinc compounds, and organic cobalt compounds, and resin additives such as adhesives, thickeners, defoamers, leveling agents, adhesion-imparting agents, and colorants.
[0124] <Physical Properties of Resin Composition>
[0125] The cured product obtained by heat curing the resin composition of the present invention at 180°C for 30 minutes and then heat curing at 180°C for 60 minutes shows excellent peeling strength with the metal layer, especially the metal layer formed by plating. That is, an insulating layer with excellent peeling strength is obtained. In detail, the following characteristics are shown: after the resin composition of the present invention is heat treated at 180°C for 30 minutes, a metal layer is formed by plating on the roughened surface obtained by roughening the surface of the cured product, and when the cured product is heat treated at 180°C for 60 minutes, the peeling strength between the cured product and the metal layer is excellent. As the peeling strength, it is preferably 0.4kgf / cm or more, more preferably 0.45kgf / cm or more, and further preferably 0.5kgf / cm or more. On the other hand, the upper limit of the peeling strength is not particularly limited, and can be 1.5kgf / cm or less, 1kgf / cm or less, etc. The evaluation of the peeling strength can be measured according to the method described in <Measurement and evaluation of the peeling strength (peeling strength) of the metal layer> described later. The metal layer is preferably a metal layer containing copper, and more preferably a metal layer formed by plating.
[0126] The cured product obtained by heat curing the resin composition of the present invention at 180°C for 90 minutes shows the property of excellent thermal conductivity. That is, an insulating layer with excellent thermal conductivity is obtained. As the thermal conductivity, it is preferably 1.5W / m·K or more, more preferably 1.8W / m·K or more, and further preferably 2.0W / m·K or more. The upper limit of the thermal conductivity may be 5.0W / m·K or less, 4.0W / m·K or less, or 3.5W / m·K or less. The evaluation of the thermal conductivity can be measured according to the method described in <Determination of Thermal Conductivity of Cured Material> described later.
[0127] The cured product obtained by heat curing the resin composition of the present invention at 180° C. for 90 minutes shows a characteristic of low elastic modulus at 23° C. That is, an insulating layer with a low elastic modulus is obtained. The elastic modulus is preferably 25 GPa or less, more preferably 20 GPa or less, and further preferably 15 GPa or less. The lower limit may be 0.1 GPa or more. The elastic modulus can be measured by the method described in <Determination of elastic modulus> described later.
[0128] The cured product obtained by thermally curing the resin composition of the present invention at 100° C. for 30 minutes and then at 180° C. for 30 minutes shows a characteristic of low warpage. That is, an insulating layer with low warpage is obtained. The average warpage of each of the four corners is preferably less than 1 cm. The warpage can be measured by the method described in <Evaluation of Warpage> described later.
[0129] The resin composition of the present invention shows a characteristic of low melt viscosity. This can improve the lamination of the resin composition layer of the resin sheet described later, and obtain a cured product of the resin composition with high peel strength. The melt viscosity is preferably 500 poise or more, more preferably 1000 poise or more, and further preferably 1500 poise or more, preferably 8500 poise or less, more preferably 8000 poise or less, and further preferably 7500 poise or less, or 7000 poise or less. The melt viscosity can be measured according to the method described in <Determination of Melt Viscosity> described later.
[0130] The resin composition of the present invention can obtain an insulating layer with excellent thermal conductivity and peel strength. Therefore, the resin composition of the present invention can be suitably used as: a resin composition for forming an insulating layer of a semiconductor chip package (resin composition for insulating layer of semiconductor chip package), a resin composition for forming an insulating layer of a circuit substrate (including a printed wiring board) (resin composition for insulating layer of circuit substrate); and further, it can be suitably used as: a resin composition for forming an interlayer insulating layer on which a conductor layer is formed by plating (a resin composition for interlayer insulating layer of a circuit substrate on which a conductor layer is formed by plating, i.e., a circuit substrate on which a circuit is formed by a semi-additive process).
[0131] Furthermore, the resin composition can be suitably used as a resin composition for sealing a semiconductor chip (resin composition for semiconductor chip sealing) or a resin composition for forming wiring on a semiconductor chip (resin composition for forming semiconductor chip wiring).
[0132] [Resin sheet]
[0133] The resin sheet of the present invention includes a support and a resin composition layer formed from the resin composition of the present invention and provided on the support.
[0134] From the viewpoint of thinning, the thickness of the resin composition layer is preferably 200 μm or less, more preferably 150 μm or less, and further preferably 100 μm or less, 80 μm or less, 60 μm or less, 50 μm or less, or 40 μm or less. The lower limit of the thickness of the resin composition layer is not particularly limited, and can usually be 1 μm or more, 5 μm or more, 10 μm or more, etc.
[0135] Examples of the support include films made of plastic materials, metal foils, and release papers, and films made of plastic materials and metal foils are preferred.
[0136] When a film formed of a plastic material is used as a support, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes referred to as "PET") and polyethylene naphthalate (hereinafter sometimes referred to as "PEN"), polycarbonate (hereinafter sometimes referred to as "PC"), acrylics such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among them, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.
[0137] When a metal foil is used as a support, examples of the metal foil include copper foil and aluminum foil, preferably copper foil. As the copper foil, a foil formed of copper alone or an alloy of copper and other metals (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) can be used.
[0138] The surface of the support to be in contact with the resin composition layer may be subjected to matte treatment or corona treatment.
[0139] In addition, as a support, a support with a release layer having a release layer on the surface bonded to the resin composition layer can be used. As a release agent used in the release layer of the support with a release layer, for example, one or more release agents selected from alkyd resins, polyolefin resins, polyurethane resins, and silicone resins can be cited. The support with a release layer can use a commercial product, for example, a PET film having a release layer with an alkyd resin-based release agent as the main component, i.e., "SK-1", "AL-5", "AL-7" manufactured by Lintec, "Lumière T60" manufactured by Toray Industries, "Purex" manufactured by Teijin, "UNIPEEL" manufactured by UNITIKA, etc. can be cited.
[0140] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, and more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, the thickness of the entire support with a release layer is preferably in the above range.
[0141] The resin sheet can be produced, for example, by preparing a resin varnish in which a resin composition is dissolved in an organic solvent, applying the resin varnish on a support using a die coater, compression molding or the like, and drying the varnish to form a resin composition layer.
[0142] Examples of the organic solvent include ketones such as acetone, methyl ethyl ketone (MEK), and cyclohexanone, acetates such as ethyl acetate, butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate, and carbitol acetate, carbitols such as cellosolve and butyl carbitol, aromatic hydrocarbons such as toluene and xylene, and amide solvents such as dimethylformamide, dimethylacetamide (DMAc), and N-methylpyrrolidone. The organic solvent may be used alone or in combination of two or more.
[0143] Drying can be carried out by known methods such as heating and blowing hot air. The drying conditions are not particularly limited, and drying is performed so that the content of the organic solvent in the resin composition layer is 10% by mass or less, preferably 5% by mass or less. Although it also varies with the boiling point of the organic solvent in the resin varnish, for example, when a resin varnish containing 30% to 60% by mass of an organic solvent is used, the resin composition layer can be formed by drying at 50°C to 150°C for 3 minutes to 10 minutes.
[0144] In the resin sheet, a protective film based on the support can be further laminated on the surface of the resin composition layer that is not bonded to the support (i.e., the surface on the opposite side of the support). The thickness of the protective film is not particularly limited, for example, 1 μm to 40 μm. By laminating the protective film, the adhesion or scratch of dirt on the surface of the resin composition layer can be prevented. The resin sheet can be rolled up for storage. In the case where the resin sheet has a protective film, it can be used by peeling off the protective film.
[0145] The resin sheet can be suitably used to form an insulating layer in the manufacture of semiconductor chip packaging (insulating resin sheet for semiconductor chip packaging). For example, the resin sheet can be suitably used to form an insulating layer of a circuit substrate (insulating resin sheet for circuit substrate), and further can be suitably used to form an interlayer insulating layer on which a conductor layer is formed by plating (interlayer insulating layer for circuit substrates formed by plating). Examples of packages using the above substrates include FC-CSP, MIS-BGA packages, and ETS-BGA packages.
[0146] In addition, the resin sheet can be suitably used for sealing semiconductor chips (resin sheets for semiconductor chip sealing), or for forming wiring on semiconductor chips (resin sheets for semiconductor chip wiring formation), and can also be suitably used for, for example, Fan-out type WLP (Wafer Level Package, wafer level packaging), Fan-in type WLP, Fan-out type PLP (Panel Level Package, panel level packaging), Fan-in type PLP, etc. In addition, it can also be suitably used for MUF (Molding Under Filling, molding bottom filling) materials used after connecting the semiconductor chip to the substrate, etc. In addition, the resin sheet can be suitably used for other wide applications requiring high insulation reliability, such as the insulating layer of the circuit substrate for forming a printed wiring board, etc.
[0147] Instead of the resin sheet, a prepreg formed by impregnating a sheet-like fiber base material with the resin composition of the present invention may be used.
[0148] The sheet-like fiber substrate used in the prepreg is not particularly limited, and glass cloth, aramid nonwoven fabric, liquid crystal polymer nonwoven fabric, etc., which are commonly used as prepreg substrates, can be used. From the viewpoint of thinning, the thickness of the sheet-like fiber substrate is preferably 900 μm or less, more preferably 800 μm or less, further preferably 700 μm or less, and further preferably 600 μm or less. The lower limit of the thickness of the sheet-like fiber substrate is not particularly limited, and can usually be 1 μm or more, 1.5 μm or more, 2 μm or more, etc.
[0149] The prepreg can be produced by a known method such as a hot melt method or a solvent method.
[0150] The thickness of the prepreg may be in the same range as that of the resin composition layer in the above-mentioned resin sheet.
[0151] [Circuit board]
[0152] The circuit board of the present invention includes an insulating layer formed of a cured product of the resin composition of the present invention.
[0153] The method for manufacturing a circuit substrate of the present invention comprises the following steps:
[0154] Step (1), preparing a substrate with a wiring layer, comprising a substrate and a wiring layer provided on at least one surface of the substrate,
[0155] Step (2), laminating the resin sheet of the present invention on a substrate having a wiring layer in such a manner that the wiring layer is embedded in the resin composition layer, and thermally curing the substrate to form an insulating layer,
[0156] Step (3), connecting the wiring layers to each other;
[0157] In addition, the method for producing a circuit board may include a step (4) of removing the base material.
[0158] There are no particular restrictions on process (3) as long as the wiring layers are connected between layers. Preferably, it is a process of forming a through hole on the insulating layer to form the wiring layer; and at least one of a process of grinding or grinding the insulating layer to expose the wiring layer.
[0159] <Step (1)>
[0160] Step (1) is a step of preparing a substrate with a wiring layer having a substrate and a wiring layer provided on at least one side of the substrate. Generally, for a substrate with a wiring layer, a first metal layer and a second metal layer as a part of the substrate are sequentially provided on both sides of the substrate, and a wiring layer is provided on the surface of the second metal layer opposite to the substrate side. In detail, a dry film (photosensitive resist film) is laminated on the substrate, and a photomask is used to expose and develop under prescribed conditions to form a patterned dry film. The developed patterned dry film is used as a plating mask, and an electrolytic plating method is used to form a wiring layer, and then the patterned dry film is peeled off. It should be noted that the first metal layer and the second metal layer may not be provided.
[0161] As the substrate, for example, glass epoxy substrates, metal substrates (stainless steel, cold rolled steel sheet (SPCC) etc.), polyester substrates, polyimide substrates, BT resin substrates, thermosetting polyphenylene ether substrates etc. can be listed, and a metal layer such as copper foil can be formed on the surface of the substrate. In addition, a strippable first metal layer and a second metal layer (for example, Mitsui Kinzoku's ultra-thin copper foil with carrier copper foil, trade name "Micro Thin") etc. can be formed on the surface.
[0162] The dry film is not particularly limited as long as it is a photosensitive dry film formed from a photoresist composition, and for example, a dry film of a phenolic resin, an acrylic resin, or the like can be used. A commercially available dry film can be used.
[0163] The conditions for laminating the substrate and the dry film are the same as those for laminating the substrate and the dry film in the step (2) described later so as to bury the resin sheet in the wiring layer, and the preferred range is also the same.
[0164] After the dry film is laminated on a substrate, the dry film is exposed and developed under predetermined conditions using a photomask to form a desired pattern.
[0165] The line width (line, circuit width) / line spacing (space, width between circuits) ratio of the wiring layer is not particularly limited, and is preferably 20 / 20 μm or less (i.e., the pitch is 40 μm or less), more preferably 10 / 10 μm or less, further preferably 5 / 5 μm or less, further preferably 1 / 1 μm or less, and particularly preferably 0.5 / 0.5 μm or more. The spacing does not need to be the same throughout the wiring layer. The minimum spacing of the wiring layer can be 40 μm or less, 36 μm or less, or 30 μm or less.
[0166] After the dry film is patterned, a wiring layer is formed and the dry film is peeled off. Here, the wiring layer can be formed by a plating method using the dry film formed with a desired pattern as a plating mask.
[0167] The conductor material used for the wiring layer is not particularly limited. In a suitable embodiment, the wiring layer comprises one or more metals selected from gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The wiring layer may be a single metal layer or an alloy layer. As the alloy layer, for example, an alloy layer formed by an alloy of two or more metals selected from the above metals (for example, nickel-chromium alloy, copper-nickel alloy and copper-titanium alloy) can be listed. Among them, from the viewpoints of versatility, cost, ease of pattern formation, etc. of the formation of the wiring layer, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper, or an alloy layer of nickel-chromium alloy, copper-nickel alloy, or copper-titanium alloy is preferred, and a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper, or an alloy layer of nickel-chromium alloy is more preferred, and a single metal layer of copper is further preferred.
[0168] The thickness of the wiring layer depends on the desired design of the wiring board, and is preferably 3μm to 35μm, more preferably 5μm to 30μm, and further preferably 10 to 20μm, or 15 to 20μm. In step (3), when the insulating layer is polished or ground to expose the wiring layer and the wiring layer is connected between layers, it is preferred that the thickness of the wiring for interlayer connection is different from that of the wiring that is not connected. The thickness of the wiring layer can be adjusted by repeatedly performing the aforementioned pattern formation. Among the wiring layers, the thickness of the thickest wiring layer (conductive column) depends on the desired design of the wiring board, and is preferably greater than 2μm and less than 100μm. In addition, the wiring for interlayer connection can be formed into a convex shape.
[0169] After forming the wiring layer, the dry film is peeled off. The peeling of the dry film can be carried out using an alkaline stripping solution such as a sodium hydroxide solution. If necessary, the unnecessary wiring pattern can be removed by etching to form a desired wiring pattern. The spacing of the formed wiring layer is as described above.
[0170] <Step (2)>
[0171] Step (2) is a step of laminating the resin sheet of the present invention on a substrate with a wiring layer so that the wiring layer is embedded in the resin composition layer, and thermally curing the substrate to form an insulating layer. Specifically, the substrate with a wiring layer obtained in the aforementioned step (1) is laminated so that the wiring layer is embedded in the resin composition layer of the resin sheet, and the resin composition layer of the resin sheet is thermally cured to form an insulating layer.
[0172] The wiring layer and the resin sheet can be laminated by, for example, heat-pressing the resin sheet to the wiring layer from the support side after removing the protective film of the resin sheet. As a member for heat-pressing the resin sheet to the wiring layer (hereinafter also referred to as a "heat-pressing member"), for example, a heated metal plate (SUS end plate (mirror plate) etc.) or a metal roller (SUS roller) etc. can be cited. It should be noted that it is preferred that the heat-pressing member is not directly pressed against the resin sheet, but is pressed through an elastic material such as heat-resistant rubber in order to make the resin sheet fully follow the surface unevenness of the wiring layer.
[0173] The lamination of the wiring layer and the resin sheet can be performed by vacuum lamination after removing the protective film of the resin sheet. In the vacuum lamination method, the heating and pressing temperature is preferably in the range of 60°C to 160°C, more preferably in the range of 80°C to 140°C, the heating and pressing pressure is preferably in the range of 0.098MPa to 1.77MPa, more preferably in the range of 0.29MPa to 1.47MPa, and the heating and pressing time is preferably in the range of 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. The lamination is preferably performed under reduced pressure conditions of 13hPa or less.
[0174] After lamination, the laminated resin sheet can be smoothed by applying pressure to the heat-pressing member under normal pressure (atmospheric pressure), for example, from the support body side. The pressurizing conditions for the smoothing treatment can be set to the same conditions as the heat-pressing conditions for the above-mentioned lamination. It should be noted that the above-mentioned commercially available vacuum laminator can be used to continuously perform lamination and smoothing treatment.
[0175] The resin composition layer is laminated on the substrate with the wiring layer in such a manner that the wiring layer is buried, and then the resin composition layer is thermally cured to form an insulating layer. For example, the thermal curing conditions of the resin composition layer vary depending on the type of the resin composition, but the curing temperature can be set in the range of 120° C. to 240° C., and the curing time can be set in the range of 5 minutes to 120 minutes. Before thermally curing the resin composition layer, the resin composition layer can be preheated at a temperature lower than the curing temperature.
[0176] The support of the resin sheet can be peeled off after the resin sheet is laminated on the substrate with the wiring layer and heat cured, or the support can be peeled off before the resin sheet is laminated on the substrate with the wiring layer. In addition, the support can be peeled off before the roughening treatment step described later.
[0177] After the resin composition layer is thermally cured to form an insulating layer, the surface of the insulating layer may be polished. The polishing method is not particularly limited, and a known method may be used, for example, the surface of the insulating layer may be polished using a flat grinding disc.
[0178] <Step (3)>
[0179] Step (3) is a step of connecting the wiring layers between layers. Specifically, it is a step of forming a through hole on the insulating layer, forming a conductor layer, and connecting the wiring layers between layers. Alternatively, it is a step of grinding or polishing the insulating layer to expose the wiring layer and connecting the wiring layers between layers. The conductor layer is sometimes called the wiring layer.
[0180] In the case of forming a through hole on the insulating layer, forming a conductor layer, and connecting the wiring layer between layers, the formation of the through hole is not particularly limited, and laser irradiation, etching, mechanical drilling, etc. can be cited, preferably laser irradiation. The laser irradiation can be performed using any suitable laser processing machine using a carbon dioxide laser, a YAG laser, an excimer laser, etc. as a light source. In detail, laser irradiation is performed from the surface side of the support of the resin sheet, penetrating the support and the insulating layer to form a through hole that exposes the wiring layer.
[0181] The conditions for laser irradiation are not particularly limited, and laser irradiation can be performed by any appropriate procedure according to a conventional method corresponding to the selected means.
[0182] The shape of the through hole, that is, the shape of the opening outline when viewed in the extending direction, is not particularly limited, but is usually a circle (substantially a circle).
[0183] After forming the through hole, a process for removing the smear in the through hole, i.e., a so-called desmear process, may be performed. When the conductor layer described later is formed by a plating process, the through hole may be subjected to, for example, a wet desmear process, and when the conductor layer is formed by a sputtering process, the through hole may be subjected to, for example, a dry desmear process such as a plasma treatment process. In addition, the desmear process may also serve as a roughening process.
[0184] The through hole and the insulating layer may be subjected to a roughening treatment before forming the conductor layer. The roughening treatment may be carried out using commonly known steps and conditions. Examples of dry roughening treatment include plasma treatment, and examples of wet roughening treatment include a method of sequentially performing a swelling treatment using a swelling solution, a roughening treatment using an oxidant, and a neutralization treatment using a neutralizing solution.
[0185] The surface roughness (Ra) of the insulating layer surface after the roughening treatment is preferably 350 nm or more, more preferably 400 nm or more, and further preferably 450 nm or more. The upper limit is preferably 700 nm or less, more preferably 650 nm or less, and further preferably 600 nm or less. The surface roughness (Ra) can be measured, for example, using a non-contact surface roughness meter.
[0186] After forming the through hole, a conductor layer is formed. There is no particular limitation on the conductor material constituting the conductor layer. The conductor layer can be formed by any suitable method known in the past, such as plating, sputtering, and evaporation, and is preferably formed by plating. In a suitable embodiment, plating is performed on the surface of the insulating layer using a previously known technique such as a semi-additive method or a full-additive method to form a conductor layer having a desired wiring pattern. Among them, a semi-additive method is preferred. In addition, when the support in the resin sheet is a metal foil, a conductor layer having a desired wiring pattern can be formed using a previously known technique such as a subtractive method. The conductor layer can be a single-layer structure or a multilayer structure obtained by laminating two or more single metal layers or alloy layers formed by different types of metals or alloys.
[0187] In the case of formation by plating, in detail, a plating seed layer is formed on the surface of the insulating layer by electroless plating (chemical plating). Next, a mask pattern is formed on the formed plating seed layer to expose a portion of the plating seed layer corresponding to the desired wiring pattern. An electrolytic plating layer is formed on the exposed plating seed layer by electrolytic plating. At this time, while forming the electrolytic plating layer, the through hole can be buried by electrolytic plating to form a filled via. After the electrolytic plating layer is formed, the mask pattern is removed. Then, the unnecessary plating seed layer can be removed by etching, etc. to form a conductor layer with a desired wiring pattern. It should be noted that when forming the conductor layer, the dry film used to form the mask pattern is the same as the above-mentioned dry film.
[0188] The conductor layer may include not only linear wiring but also, for example, electrode pads (land, pads) on which external terminals can be mounted. Alternatively, the conductor layer may be composed only of electrode pads.
[0189] Alternatively, the conductor layer may be formed by forming a plating seed layer, forming an electrolytic plating layer and filling holes without using a mask pattern, and then performing patterning by etching.
[0190] In the case of a process of grinding or polishing the insulating layer, exposing the wiring layer, and connecting the wiring layer to the interlayer, the grinding method or grinding method of the insulating layer is not particularly limited as long as the wiring layer can be exposed and the grinding or polishing surface can be horizontal. The grinding method or grinding method known in the past can be applied, and examples thereof include a chemical mechanical polishing method using a chemical mechanical polishing device, a mechanical polishing method such as buffing, and a surface grinding method using a grinding stone rotation. Similar to the process of forming a through hole on the insulating layer, forming a conductor layer, and connecting the wiring layer to the interlayer, a drilling smear removal process and a roughening process can be performed, and a conductor layer can also be formed. In addition, it is not necessary to expose the entire wiring layer, and a portion of the wiring layer can be exposed.
[0191] <Step (4)>
[0192] Step (4) is a step of removing the substrate to form the circuit substrate of the present invention. The method for removing the substrate is not particularly limited. In a suitable embodiment, at the interface between the first metal layer and the second metal layer, the substrate is peeled off from the circuit substrate, and the second metal layer is etched away using, for example, a cupric chloride aqueous solution. If necessary, the substrate may also be peeled off while the conductor layer is protected by a protective film.
[0193] In other embodiments, the circuit board can be manufactured using the above-mentioned prepreg. The manufacturing method is basically the same as that in the case of using a resin sheet.
[0194] [Semiconductor chip packaging]
[0195] A first aspect of the semiconductor chip package of the present invention is a semiconductor chip package in which a semiconductor chip is mounted on the circuit substrate. The semiconductor chip package can be manufactured by bonding the semiconductor chip to the circuit substrate.
[0196] The bonding conditions are not particularly limited, as long as the terminal electrodes of the semiconductor chip are connected to the circuit wiring of the circuit substrate by conductors, and the known conditions that can be used in the flip chip mounting of the semiconductor chip can be used. In addition, the semiconductor chip and the circuit substrate can also be bonded via an insulating adhesive.
[0197] In a suitable embodiment, the semiconductor chip is crimped to the circuit board. As the crimping conditions, for example, the crimping temperature can be set to a range of 120° C. to 240° C. (preferably a range of 130° C. to 200° C., more preferably a range of 140° C. to 180° C.), and the crimping time can be set to a range of 1 second to 60 seconds (preferably 5 seconds to 30 seconds).
[0198] In another preferred embodiment, the semiconductor chip is bonded to the circuit board by reflow soldering. The reflow soldering conditions can be set to a range of 120°C to 300°C, for example.
[0199] After the semiconductor chip is bonded to the circuit substrate, for example, the semiconductor chip can be filled with a molded bottom filling material to obtain a semiconductor chip package. The method of filling with a molded bottom filling material can be implemented using a known method. The resin composition or resin sheet of the present invention can also be used as a molded bottom filling material.
[0200] The second embodiment of the semiconductor chip package of the present invention is as follows. Figure 1 An example of a semiconductor chip package (Fan-out type WLP) is shown. Figure 1 The semiconductor chip package (Fan-out type WLP) 100 of the example shown is a semiconductor chip package obtained by manufacturing a sealing layer 120 using the resin composition or resin sheet of the present invention. The semiconductor chip package 100 includes: a semiconductor chip 110, a sealing layer 120 formed in a manner of covering the periphery of the semiconductor chip 110, a rewiring forming layer (insulating layer) 130 on the surface of the semiconductor chip 110 opposite to the sealing layer covering side, a conductor layer (rewiring layer) 140, a solder resist layer 150, and a bump 160. The manufacturing method of the semiconductor chip package includes the following steps:
[0201] Step (A), laminating a temporary fixing film on a substrate,
[0202] Step (B), temporarily fixing the semiconductor chip on the temporary fixing film,
[0203] Step (C), laminating the resin composition layer of the resin sheet of the present invention on the semiconductor chip, or coating the resin composition of the present invention on the semiconductor chip and thermally curing it to form a sealing layer,
[0204] Step (D), peeling the substrate and the temporary fixing film from the semiconductor chip,
[0205] Step (E) of forming a rewiring formation layer (insulating layer) on the surface of the semiconductor chip from which the substrate and the temporary fixing film have been peeled off,
[0206] Step (F), forming a conductor layer (rewiring layer) on the rewiring forming layer (insulating layer), and
[0207] Step (G), forming a solder resist layer on the conductor layer;
[0208] In addition, the method for manufacturing a semiconductor chip package may include a step (H) of cutting a plurality of semiconductor chip packages into individual semiconductor chip packages to separate them into pieces.
[0209] <Step (A)>
[0210] Step (A) is a step of laminating the temporary fixing film on the substrate. The lamination conditions of the substrate and the temporary fixing film are the same as those of the lamination of the wiring layer and the resin sheet in step (2) in the method for producing a circuit board, and the preferred range is also the same.
[0211] The material used for the substrate is not particularly limited. Examples of the substrate include silicon wafers; glass wafers; glass substrates; metal substrates such as copper, titanium, stainless steel, and cold-rolled steel sheets (SPCC); substrates such as FR-4 substrates in which epoxy resins or the like are infiltrated into glass fibers and then subjected to a heat curing treatment; and substrates formed from bismaleimide triazine resins such as BT resins.
[0212] The temporary fixing film may be made of any material that can be peeled off from the semiconductor chip in the step (D) described later and can temporarily fix the semiconductor chip. Commercial products may be used as the temporary fixing film. Examples of commercial products include REVALPHA manufactured by Nitto Denko Corporation.
[0213] <Process (B)>
[0214] Step (B) is a step of temporarily fixing the semiconductor chip on the temporary fixing film. The temporary fixing of the semiconductor chip can be performed using a known device such as a flip chip bonder or a die bonder. The layout and number of configurations of the semiconductor chip can be appropriately set according to the shape and size of the temporary fixing film, the number of production of the target semiconductor package, etc. For example, it can be arranged in a matrix of multiple rows and columns for temporary fixing.
[0215] <Process (C)>
[0216] Step (C) is a step of laminating the resin composition layer of the resin sheet of the present invention on the semiconductor chip, or applying the resin composition of the present invention on the semiconductor chip and thermally curing it to form a sealing layer. In step (C), it is preferred that the resin composition layer of the resin sheet is laminated on the semiconductor chip and thermally cured to form a sealing layer.
[0217] The lamination of the semiconductor chip and the resin sheet can be performed by, for example, heating and pressing the resin sheet to the semiconductor chip from the support body side after removing the protective film of the resin sheet. As a component for heating and pressing the resin sheet to the semiconductor chip (hereinafter also referred to as "heating and pressing component"), for example, a heated metal plate (SUS end plate, etc.) or a metal roller (SUS roller) etc. can be cited. It should be noted that it is preferred that the heating and pressing component is not directly pressed against the resin sheet, but in order to make the resin sheet fully follow the surface unevenness of the semiconductor chip, it is pressed through an elastic material such as heat-resistant rubber.
[0218] In addition, the semiconductor chip and the resin sheet can also be laminated by vacuum lamination after removing the protective film of the resin sheet. The lamination conditions in the vacuum lamination method are the same as the lamination conditions of the wiring layer and the resin sheet in step (2) in the method for manufacturing the circuit board, and the preferred range is also the same.
[0219] The support of the resin sheet may be peeled off after laminating the resin sheet on the semiconductor chip and thermally curing it, or may be peeled off before laminating the resin sheet on the semiconductor chip.
[0220] The coating conditions of the resin composition are the same as those for forming the resin composition layer in the resin sheet of the present invention, and the preferred range is also the same.
[0221] <Process (D)>
[0222] Step (D) is a step of peeling the substrate and the temporary fixing film from the semiconductor chip. The peeling method can be appropriately changed according to the material of the temporary fixing film, and examples thereof include a method of peeling the temporary fixing film by heating it to foam (or expand) it, and a method of peeling it by irradiating ultraviolet rays from the substrate side to reduce the adhesive force of the temporary fixing film, etc.
[0223] In the method of peeling off the temporary fixing film by heating it to make it foam (or expand), the heating conditions are usually 100°C to 250°C for 1 second to 90 seconds or 5 minutes to 15 minutes. In the method of peeling off the temporary fixing film by irradiating it with ultraviolet rays from the substrate side to reduce the adhesive force of the temporary fixing film, the irradiation amount of ultraviolet rays is usually 10mJ / cm 2 ~1000mJ / cm 2 .
[0224] <Step (E)>
[0225] Step (E) is a step of forming a rewiring formation layer (insulating layer) on the surface of the semiconductor chip from which the substrate and the temporary fixing film have been peeled off.
[0226] The material forming the rewiring forming layer (insulating layer) is not particularly limited as long as it has insulating properties when forming the rewiring forming layer (insulating layer). From the perspective of ease of manufacturing the semiconductor chip package, photosensitive resins and thermosetting resins are preferred. As the thermosetting resin, a resin composition having the same composition as the resin composition used to form the resin sheet of the present invention can be used.
[0227] After the rewiring formation layer (insulating layer) is formed, a through hole may be formed in the rewiring formation layer (insulating layer) in order to establish interlayer connection between the semiconductor chip and the conductor layer described later.
[0228] When forming a through hole, if the material forming the rewiring forming layer (insulating layer) is a photosensitive resin, first, active energy rays are irradiated to the surface of the rewiring forming layer (insulating layer) through a mask pattern to photocure the rewiring layer in the irradiated portion.
[0229] As active energy rays, for example, ultraviolet rays, visible rays, electron beams, X-rays, etc. can be cited, and ultraviolet rays are particularly preferred. The irradiation amount and irradiation time of ultraviolet rays can be appropriately changed according to the photosensitive resin. As an exposure method, any method can be used: a contact exposure method in which a mask pattern is closely attached to the rewiring formation layer (insulating layer) and exposed, and a non-contact exposure method in which parallel light is used to expose without closely attaching the mask pattern to the rewiring formation layer (insulating layer).
[0230] Next, the rewiring forming layer (insulating layer) is developed to remove the unexposed portion, thereby forming a through hole. The development may be either wet development or dry development. A known developer may be used as the developer used in the wet development.
[0231] Examples of the development method include a dipping method, a puddle method, a spray method, a brush method, and a scraping method. From the viewpoint of resolution, the puddle method is preferred.
[0232] When the material forming the rewiring forming layer (insulating layer) is a thermosetting resin, the formation of the through hole is not particularly limited, and laser irradiation, etching, mechanical drilling, etc. can be cited, preferably by laser irradiation. Laser irradiation can be performed using any suitable laser processing machine using a carbon dioxide laser, UV-YAG laser, excimer laser, etc. as a light source.
[0233] The conditions for laser irradiation are not particularly limited, and laser irradiation can be performed by any appropriate procedure according to a conventional method corresponding to the selected means.
[0234] The shape of the through hole, i.e., the shape of the opening profile when viewed along the extension direction, is not particularly limited, and is generally circular (substantially circular). The top diameter of the through hole (the diameter of the opening on the surface of the rewiring forming layer (insulating layer)) is preferably 50 μm or less, more preferably 30 μm or less, and further preferably 20 μm or less. The lower limit is not particularly limited, but is preferably 10 μm or more, more preferably 15 μm or more, and further preferably 20 μm or more.
[0235] <Process (F)>
[0236] Step (F) is a step of forming a conductor layer (rewiring layer) on the rewiring forming layer (insulating layer). The method of forming a conductor layer on the rewiring forming layer (insulating layer) is the same as the method of forming a conductor layer after forming a through hole on the insulating layer in step (3) of the manufacturing method of the circuit board, and the preferred range is also the same. It should be noted that steps (E) and (F) may be repeated to alternately stack (build-up) the conductor layer (rewiring layer) and the rewiring forming layer (insulating layer).
[0237] <Step (G)>
[0238] Step (G) is a step of forming a solder resist layer on the conductor layer.
[0239] The material forming the solder resist layer is not particularly limited as long as it is a material having insulating properties when forming the solder resist layer. From the viewpoint of the ease of manufacturing the semiconductor chip package, photosensitive resins and thermosetting resins are preferred. As the thermosetting resin, a resin composition having the same composition as the resin composition for forming the resin sheet of the present invention can be used.
[0240] In step (G), bump processing to form a bump may be performed as needed. The bump processing may be performed using a known method such as solder ball or solder plating. In addition, the formation of a through hole in the bump processing may be performed in the same manner as in step (E).
[0241] <Process (H)>
[0242] The method for manufacturing a semiconductor chip package may further include step (H) in addition to steps (A) to (G). Step (H) is a step of cutting a plurality of semiconductor chip packages into individual semiconductor chip packages to separate them into pieces.
[0243] The method of dicing the semiconductor chip package into individual semiconductor chip packages is not particularly limited, and a known method can be used.
[0244] A third embodiment of the semiconductor chip package of the present invention is, for example Figure 1As shown in one example, a semiconductor chip package is produced by using the resin composition or resin sheet of the present invention to form a redistribution layer (insulating layer) 130 and a solder resist layer 150 in a semiconductor chip package (Fan-out type WLP).
[0245] [Semiconductor devices]
[0246] As semiconductor devices equipped with the semiconductor chip package of the present invention, there can be listed various semiconductor devices for use in electrical products (for example, computers, mobile phones, smart phones, tablet devices, wearable devices, digital cameras, medical equipment, and televisions, etc.) and transportation vehicles (for example, motorcycles, automobiles, trains, ships, and aircraft, etc.).
[0247] [Example]
[0248] The present invention will be described in more detail below by way of examples, but the present invention is not limited to these examples. It should be noted that, in the following description, "parts" and "%" indicating amounts refer to "parts by mass" and "% by mass" respectively, unless otherwise specified.
[0249] <Preparation of Sample for Peel Strength Measurement>
[0250] (1) Base treatment of inner layer circuit board
[0251] Both sides of a glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.3 mm, R5715ES manufactured by Panasonic Corporation) with an inner layer circuit formed thereon were immersed in CZ8100 manufactured by MEC Corporation to perform a copper surface roughening treatment.
[0252] (2) Lamination of resin sheets
[0253] Using an intermittent vacuum pressurized laminator (2-Stage Buildup Laminator (2-stage stacking laminator) "CVP700" manufactured by Nikko-Materials), the resin sheets prepared in the examples and comparative examples are laminated on both sides of the inner layer circuit substrate to bond the resin composition layer to the inner layer circuit substrate. The lamination is carried out as follows: After reducing the pressure for 30 seconds to bring the air pressure to below 13 hPa, crimp at 100°C and 0.74 MPa for 30 seconds. Then, hot pressing is performed at 100°C and 0.5 MPa for 60 seconds. The obtained laminate with a resin composition layer is heat treated at 180°C for 30 minutes to cure the resin composition layer to obtain a laminate with a cured product.
[0254] (3) Roughening treatment
[0255] The obtained laminate with the cured product was immersed in Swelling Dip Securiganth P (swelling solution) containing diethylene glycol monobutyl ether manufactured by ATOTECH JAPAN for 5 minutes at 60°C, then immersed in Concentrate Compact P (KMnO4: 60 g / L, NaOH: 40 g / L aqueous solution, oxidant (roughening solution)) manufactured by ATOTECH JAPAN for 10 minutes at 80°C, and finally immersed in Reduction Solution Securiganth P (neutralizing solution) manufactured by ATOTECH JAPAN for 5 minutes at 40°C to roughen the surface of the cured product. The laminate obtained by the roughening treatment was used as evaluation substrate A.
[0256] (4) Forming a metal layer by plating
[0257] Evaluation substrate A was immersed in an electroless plating solution containing PdCl2, and then immersed in an electroless copper plating solution. Next, copper sulfate electrolytic plating was performed to form a metal layer with a thickness of 30 μm on the roughened surface of the solidified product. Then, annealing treatment was performed at 180°C for 60 minutes. The annealed laminate was used as evaluation substrate B.
[0258] <Measurement and Evaluation of Peel Strength of Metal Layer>
[0259] A 10 mm wide and 100 mm long incision was made on the metal layer of the evaluation substrate B, one end was peeled off and clamped with a clamp (AUTO COM tester "AC-50C-SL" manufactured by TSE), and the load (kgf / cm) when 20 mm was peeled off in the vertical direction at room temperature at a speed of 50 mm / min was measured to determine the peel strength.
[0260] <Preparation of Cured Material for Elastic Modulus Evaluation>
[0261] A release PET film ("501010" manufactured by Lintec Corporation, 38 μm thick, 240 mm square) was placed on a glass cloth-based epoxy resin double-sided copper-clad laminate ("R5715ES" manufactured by Matsushita Electric Works, 0.7 mm thick, 255 mm square) in such a way that the untreated surface of the film was in contact with the glass cloth-based epoxy resin double-sided copper-clad laminate, and the four sides of the release PET film were fixed with polyimide tape (10 mm wide).
[0262] The resin sheets (167×107 mm square) prepared in the examples and comparative examples were laminated in the center using an intermittent vacuum pressurization laminator (Nikko-Materials, 2-stage stack laminator, CVP700) in such a way that the resin composition layer was in contact with the release surface of the release PET film. The lamination process was carried out as follows: after decompression for 30 seconds to reduce the air pressure to 13 hPa or less, the sheets were pressed at 100° C. and 0.74 MPa for 30 seconds.
[0263] Next, the support was peeled off, and the resin composition layer was thermally cured under curing conditions of 180° C. and 90 minutes.
[0264] After thermal curing, the polyimide tape was peeled off to remove the resin composition layer from the glass cloth substrate epoxy resin double-sided copper-clad laminate. The release PET film was further peeled off from the resin composition layer to obtain a sheet-like cured product (cured product for evaluation).
[0265] <Determination of Elastic Modulus>
[0266] The cured product for evaluation was cut into dumbbell No. 1 shape to obtain a test piece. The tensile strength of the test piece was measured using a tensile tester "RTC-1250A" manufactured by ORIENTEC, and the elastic modulus at 23°C was determined. The measurement was carried out in accordance with JIS K7127. This operation was performed 3 times, and the average value is shown in the table.
[0267] <Evaluation of Warpage Amount>
[0268] The resin sheets prepared in the examples and comparative examples were laminated on one side of a glass cloth substrate BT resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.15 mm, Mitsubishi Gas Chemical Co., Ltd. "HL832NSF LCA", size 15 cm × 18 cm) using an intermittent vacuum press laminator (Nikko-Materials, 2-stage stack laminator "CVP700"). After peeling off the release PET, the sheets were heat-cured at 100°C for 30 minutes and then at 180°C for 30 minutes, and then placed on a flat surface to check the warpage. The average warpage of each of the four corners was evaluated as "○" when it was less than 1 cm, the average warpage was evaluated as "△" when it was 1 to 2 cm, and the average warpage was evaluated as "×" when it was 2 cm or more.
[0269] <Measurement of Thermal Conductivity of Cured Material>
[0270] (1) Preparation of cured product samples
[0271] The resin varnish prepared in the examples and comparative examples was applied using a die coater on a PET film ("Lumière R80" manufactured by Toray Industries, Ltd., thickness 38 μm, softening point 130° C.) that had been subjected to a release treatment with an alkyd resin-based release agent ("AL-5" manufactured by Lintec) so that the thickness of the resin composition layer after drying was 100 μm, and dried at 80° C. to 100° C. (90° C. on average) for 7 minutes to obtain a resin composition layer.
[0272] The resin composition layers were laminated after being stacked in three layers using an intermittent vacuum pressurizing laminator (Nikko-Materials, 2-stage stacking laminator "CVP700"), and the resin composition layers were cured under curing conditions of 180°C and 90 minutes to obtain a cured product sample. The lamination was performed as follows: the pressure was reduced for 30 seconds to a pressure of 13 hPa or less, and then pressurized at 100°C and 0.4 MPa for 20 seconds.
[0273] (2) Determination of thermal diffusivity α
[0274] The thermal diffusivity α (m) in the thickness direction of the cured product sample was measured by temperature wave analysis using “ai-Phase Mobile 1u” manufactured by ai-Phase. 2 / s). The same sample was measured three times and the average value was calculated.
[0275] (3) Determination of specific heat capacity Cp
[0276] The cured sample was measured by heating from -40°C to 80°C at a rate of 10°C / min using a differential scanning calorimeter (DSC7020 manufactured by SII Nano Technology) to calculate the specific heat capacity Cp (J / kg·K) of the cured sample at 25°C.
[0277] (4) Determination of density ρ
[0278] The density of the cured sample (kg / m 3 ).
[0279] (5) Calculation of thermal conductivity λ
[0280] The thermal diffusivity α(m 2 / s), specific heat capacity Cp (J / kg·K) and density ρ (kg / m 3 ) is substituted into the following formula (I) to calculate the thermal conductivity λ (W / m·K);
[0281] λ = α × Cp × ρ (I).
[0282] <Determination of Melt Viscosity>
[0283] The melt viscosity of the resin composition layer in the resin sheets prepared in the examples and comparative examples was measured using Rheosol-G3000 manufactured by UBM, with a resin amount of 1 g, a parallel plate of 18 mm in diameter, from a starting temperature of 60°C to 200°C, a heating rate of 5°C / min, a measuring temperature interval of 2.5°C, and a vibration of 1 Hz / deg.
[0284] <Synthesis Example 1: Synthesis of Polymer Compound 1>
[0285] In a reaction container, 69 g of G-3000 (bifunctional hydroxyl-terminated polybutadiene, number average molecular weight = 5047 (GPC method), hydroxyl equivalent = 1798 g / eq., solid content 100 mass %: manufactured by Nippon Soda Co., Ltd.), 40 g of Ipsol 150 (aromatic hydrocarbon mixed solvent: manufactured by Idemitsu Petrochemical Co., Ltd.), and 0.005 g of dibutyltin dilaurate were mixed and uniformly dissolved. After becoming uniform, the temperature was raised to 50° C., and 8 g of isophorone diisocyanate (manufactured by Evonik Degussa Japan Co., Ltd., IPDI, isocyanate group equivalent = 113 g / eq.) was added while stirring, and the reaction was carried out for about 3 hours. Next, the reaction product was cooled to room temperature, and then 23 g of cresol novolac resin (KA-1160, manufactured by DIC Corporation, hydroxyl equivalent = 117 g / eq.) and 60 g of ethyl diglycol acetate (manufactured by Daicel Corporation) were added thereto, and the temperature was raised to 80°C while stirring, and the reaction was carried out for about 4 hours. FT-IR confirmed that the 2250 cm -1 The disappearance of the NCO peak was considered as the end point of the reaction, and the reactant was cooled to room temperature and then filtered with a filter cloth having a mesh size of 100 μm to obtain a polymer compound 1 having a polybutadiene structure and a phenolic hydroxyl group (non-volatile content 50 mass %).
[0286] <Synthesis Example 2: Synthesis of Polymer Compound 2>
[0287] In a reaction container, 80 g of polycarbonate diol (number average molecular weight: about 1000, hydroxyl equivalent: 500, nonvolatile content: 100%, "C-1015N" manufactured by Kuraray Co., Ltd.) and 0.01 g of dibutyltin dilaurate were uniformly dissolved in 37.6 g of diethylene glycol monoethyl ether acetate ("diethylene glycol ethyl ether acetate" manufactured by Daicel Co., Ltd.). Next, the mixture was heated to 50°C, and 27.8 g of toluene-2,4-diisocyanate (isocyanate group equivalent: 87.08) was added while stirring, and the reaction was carried out for about 3 hours. Next, the reaction product was cooled to room temperature, and then 14.3 g of benzophenonetetracarboxylic dianhydride (anhydride equivalent: 161.1), 0.12 g of triethylenediamine, and 84.0 g of diethylene glycol monoethyl ether acetate ("diethylene glycol ethyl ether acetate" manufactured by Daicel) were added thereto, and the temperature was raised to 130° C. while stirring, and the reaction was carried out for about 4 hours. FT-IR confirmed that the 2250 cm -1 The disappearance of the NCO peak was confirmed as the end point of the reaction, and the reactant was cooled to room temperature and then filtered through a filter cloth with a mesh size of 100 μm to obtain a polymer compound 2 having a carbonate structure (non-volatile component 50 mass %).
[0288] <Measurement of Average Particle Diameter of Thermally Conductive Filler>
[0289] Add 0.01g of thermally conductive filler, 0.2g of nonionic dispersant ("T208.5" manufactured by NOF Corporation) and 10g of pure water to a 20ml vial, and use an ultrasonic cleaner to perform ultrasonic dispersion for 10 minutes to prepare a sample. Then, put the sample into a laser diffraction particle size distribution measuring device ("SALD2200" manufactured by Shimadzu Corporation), and irradiate the sample with ultrasound for 10 minutes while circulating it. Then, stop the ultrasound, measure the particle size distribution while maintaining the sample circulation, and find the average particle size of the thermally conductive filler. It should be noted that the refractive index during the measurement is set to 1.45-0.001i.
[0290] <Measurement of Specific Surface Area of Thermally Conductive Filler>
[0291] The specific surface area was determined by a nitrogen BET method using an automatic specific surface area measuring apparatus ("Macsorb HM-1210" manufactured by Mountech Corporation).
[0292] <Thermal conductive filler used>
[0293] Alumina 1: A mixture of aluminas with different average particle sizes and specific surface areas, average particle size 3 μm, specific surface area 1.5 m 2 / g, aluminum oxide surface-treated with "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd.;
[0294] Alumina 2: A mixture of aluminas with different average particle sizes and specific surface areas, average particle size 3 μm, specific surface area 1.5 m 2 / g, aluminum oxide surface-treated with "KBM5783" (N-phenyl-3-aminooctyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd.;
[0295] Alumina 3: A mixture of aluminas with different average particle sizes and specific surface areas, average particle size 3 μm, specific surface area 1.5 m 2 / g, aluminum oxide surface-treated with "KBM403" (3-glycidoxypropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd.;
[0296] Alumina 4: A mixture of aluminas with different average particle sizes and specific surface areas, average particle size 3 μm, specific surface area 1.5 m 2 / g, and aluminum oxide surface-treated with "KBM903" (3-aminopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd.
[0297] <Example 1>
[0298] 6 parts of aminophenol type epoxy resin (Mitsubishi Chemical Corporation "630", epoxy equivalent: 95 g / eq), 5 parts of liquid epoxy resin (Nippon Steel & Sumitomo Metal Chemical Corporation "ZX1059", 1:1 mixture (mass ratio) of bisphenol A type epoxy resin and bisphenol F type epoxy resin, epoxy equivalent: 169 g / eq), 2 parts of biphenyl type epoxy resin (Mitsubishi Chemical Corporation "YX4000H", epoxy equivalent: 185 g / eq), 2 parts of biphenyl type epoxy resin (Nippon Kayaku Co., Ltd. "NC3100", epoxy equivalent: 258 g / eq) were dissolved in 10 parts of methyl ethyl ketone, and mixed with 1 (270 parts) of aluminum oxide, a polymer compound and a mixture of 1:1 mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin. 24 parts of material 1 (solid content 50% by mass, number average molecular weight 5500), 3 parts of an active ester curing agent ("HPC-8000-65T" manufactured by DIC Corporation, active ester equivalent 223 g / eq, toluene solution with 65% solid content), 2 parts of a solid naphthol-based curing agent ("SN485" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., hydroxyl equivalent 215 g / eq, used as a methyl ethyl ketone solution with 50% solid content), 1 part of a curing accelerator (2-phenyl-1-benzyl-1H-imidazole (1B2PZ), MEK solution with 10% solid content), and 15 parts of methyl ethyl ketone were uniformly dispersed in a high-speed rotary mixer to prepare a resin varnish 1.
[0299] Using a die coater, the resin varnish 1 was applied onto a PET film ("Lumière R80" manufactured by Toray Industries, Ltd., thickness 38 μm, softening point 130°C, sometimes referred to as "release PET") that had been subjected to a release treatment with an alkyd resin-based release agent ("AL-5" manufactured by Lintec Corporation) in such a manner that the thickness of the resin composition layer after drying was 50 μm, and dried at 80°C to 100°C (90°C on average) for 5 minutes to obtain a resin sheet 1.
[0300] <Example 2>
[0301] 6 parts of aminophenol type epoxy resin (Mitsubishi Chemical Corporation "630", epoxy equivalent: 95 g / eq), 5 parts of liquid epoxy resin (Nippon Steel & Sumitomo Metal Chemical Corporation "ZX1059", 1:1 mixture (mass ratio) of bisphenol A type epoxy resin and bisphenol F type epoxy resin, epoxy equivalent: 169 g / eq), 2 parts of biphenyl type epoxy resin (Mitsubishi Chemical Corporation "YX4000H", epoxy equivalent: 185 g / eq), 2 parts of biphenyl type epoxy resin (Nippon Kayaku Co., Ltd. "NC3100", epoxy equivalent: 258 g / eq) were dissolved in 10 parts of methyl ethyl ketone, and mixed with 1 (270 parts) of aluminum oxide, a polymer compound and a mixture of 1:1 mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin. 24 parts of material 1 (solid content 50% by mass, number average molecular weight 5500), 6 parts of active ester curing agent ("HPC-8000-65T" manufactured by DIC Corporation, active ester equivalent 223 g / eq, toluene solution with 65% solid content), 6 parts of solid naphthol curing agent ("SN485" manufactured by Nippon Steel & Sumikin Chemical Corporation, hydroxyl equivalent 215 g / eq, used as methyl ethyl ketone solution with 50% solid content), 1 part of curing accelerator (2-phenyl-1-benzyl-1H-imidazole (1B2PZ), MEK solution with 10% solid content), and 15 parts of methyl ethyl ketone were uniformly dispersed by a high-speed rotary mixer to prepare resin varnish 2. In addition, except that the resin varnish 1 in Example 1 was changed to resin varnish 2, the same operation as in Example 1 was performed to obtain a resin sheet 2.
[0302] <Example 3>
[0303] 6 parts of aminophenol type epoxy resin (Mitsubishi Chemical Corporation "630", epoxy equivalent: 95 g / eq), 5 parts of liquid epoxy resin (Nippon Steel & Sumitomo Metal Chemical Corporation "ZX1059", 1:1 mixture (mass ratio) of bisphenol A type epoxy resin and bisphenol F type epoxy resin, epoxy equivalent: 169 g / eq), 2 parts of biphenyl type epoxy resin (Mitsubishi Chemical Corporation "YX4000H", epoxy equivalent: 185 g / eq), 2 parts of biphenyl type epoxy resin (Nippon Kayaku Co., Ltd. "NC3100", epoxy equivalent: 258 g / eq) were dissolved in 10 parts of methyl ethyl ketone, and mixed with 1 (240 parts) of aluminum oxide and a polymer compound. 24 parts of material 1 (solid content 50% by mass, number average molecular weight 5500), 3 parts of active ester curing agent ("HPC-8000-65T" manufactured by DIC Corporation, active ester equivalent 223 g / eq, toluene solution with 65% solid content), 2 parts of solid naphthol curing agent ("SN485" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., hydroxyl equivalent 215 g / eq, used as methyl ethyl ketone solution with 50% solid content), 1 part of curing accelerator (2-phenyl-1-benzyl-1H-imidazole (1B2PZ), MEK solution with 10% solid content), and 15 parts of methyl ethyl ketone were uniformly dispersed by a high-speed rotary mixer to prepare resin varnish 3. In addition, except that the resin varnish 1 in Example 1 was changed to resin varnish 3, the same operation as in Example 1 was performed to obtain resin sheet 3.
[0304] <Example 4>
[0305] 6 parts of aminophenol type epoxy resin (Mitsubishi Chemical Corporation "630", epoxy equivalent: 95 g / eq), 5 parts of liquid epoxy resin (Nippon Steel & Sumitomo Metal Chemical Corporation "ZX1059", 1:1 mixture (mass ratio) of bisphenol A type epoxy resin and bisphenol F type epoxy resin, epoxy equivalent: 169 g / eq), 2 parts of biphenyl type epoxy resin (Mitsubishi Chemical Corporation "YX4000H", epoxy equivalent: 185 g / eq), 2 parts of biphenyl type epoxy resin (Nippon Kayaku Corporation "NC3100", epoxy equivalent: 258 g / eq) were dissolved in 10 parts of methyl ethyl ketone, and mixed with 270 parts of aluminum oxide, a polymer compound and a mixture of 1:1 mixture. 24 parts of material 1 (solid content 50% by mass, number average molecular weight 5500), 3 parts of active ester curing agent ("HPC-8000-65T" manufactured by DIC Corporation, active ester equivalent 223 g / eq, toluene solution with 65% solid content), 2 parts of solid naphthol curing agent ("SN485" manufactured by Nippon Steel & Sumikin Chemical Corporation, hydroxyl equivalent 215 g / eq, used as methyl ethyl ketone solution with 50% solid content), 1 part of curing accelerator (2-phenyl-1-benzyl-1H-imidazole (1B2PZ), MEK solution with 10% solid content by mass), and 15 parts of methyl ethyl ketone were uniformly dispersed by a high-speed rotary mixer to prepare resin varnish 4. In addition, except that the resin varnish 1 in Example 1 was changed to resin varnish 4, the same operation as in Example 1 was performed to obtain resin sheet 4.
[0306] <Example 5>
[0307] 6 parts of aminophenol type epoxy resin (Mitsubishi Chemical Corporation "630", epoxy equivalent: 95 g / eq), 5 parts of liquid epoxy resin (Nippon Steel & Sumitomo Metal Chemical Corporation "ZX1059", 1:1 mixture (mass ratio) of bisphenol A type epoxy resin and bisphenol F type epoxy resin, epoxy equivalent: 169 g / eq), 2 parts of biphenyl type epoxy resin (Mitsubishi Chemical Corporation "YX4000H", epoxy equivalent: 185 g / eq), 2 parts of biphenyl type epoxy resin (Nippon Kayaku Co., Ltd. "NC3100", epoxy equivalent: 258 g / eq) were dissolved in 10 parts of methyl ethyl ketone, and mixed with 1 (270 parts) of aluminum oxide, a polymer compound and a mixture of 1:1 mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin. 24 parts of product 2 (solid content 50% by mass, number average molecular weight 6000), 3 parts of active ester curing agent ("HPC-8000-65T" manufactured by DIC Corporation, active ester equivalent 223 g / eq, toluene solution with 65% solid content), 2 parts of solid naphthol curing agent ("SN485" manufactured by Nippon Steel & Sumikin Chemical Corporation, hydroxyl equivalent 215 g / eq, used as methyl ethyl ketone solution with 50% solid content), 1 part of curing accelerator (2-phenyl-1-benzyl-1H-imidazole (1B2PZ), MEK solution with 10% solid content by mass), and 15 parts of methyl ethyl ketone were uniformly dispersed by a high-speed rotary mixer to prepare resin varnish 5. In addition, except that the resin varnish 1 in Example 1 was changed to resin varnish 5, the same operation as in Example 1 was performed to obtain resin sheet 5.
[0308] <Comparative Example 1>
[0309] 6 parts of aminophenol type epoxy resin (Mitsubishi Chemical Corporation "630", epoxy equivalent: 95 g / eq), 5 parts of liquid epoxy resin (Nippon Steel & Sumitomo Metal Chemical Corporation "ZX1059", a 1:1 mixture (mass ratio) of bisphenol A type epoxy resin and bisphenol F type epoxy resin, epoxy equivalent: 169 g / eq), 2 parts of biphenyl type epoxy resin (Mitsubishi Chemical Corporation "YX4000H", epoxy equivalent: 185 g / eq), and 2 parts of biphenyl type epoxy resin (Nippon Kayaku Corporation "NC3100", epoxy equivalent: 258 g / eq) were dissolved in the mixture. Alumina 1 (270 parts), polymer compound 1 (50% by mass of solid content, number average molecular weight 5500) 24 parts, solid naphthol curing agent ("SN485" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., hydroxyl equivalent 215 g / eq, used as 50% solid content methyl ethyl ketone solution) 6 parts, curing accelerator (2-phenyl-1-benzyl-1H-imidazole (1B2PZ), 10% solid content MEK solution) 1 part, methyl ethyl ketone 15 parts were mixed with 10 parts of methyl ethyl ketone, and uniformly dispersed with a high-speed rotary mixer to prepare resin varnish 6. In addition, except that the resin varnish 1 in Example 1 was changed to resin varnish 6, the same operation as in Example 1 was performed to obtain a resin sheet 6.
[0310] <Comparative Example 2>
[0311] 6 parts of aminophenol type epoxy resin (Mitsubishi Chemical Corporation "630", epoxy equivalent: 95 g / eq), 5 parts of liquid epoxy resin (Nippon Steel & Sumitomo Metal Chemical Corporation "ZX1059", a 1:1 mixture (mass ratio) of bisphenol A type epoxy resin and bisphenol F type epoxy resin, epoxy equivalent: 169 g / eq), 2 parts of biphenyl type epoxy resin (Mitsubishi Chemical Corporation "YX4000H", epoxy equivalent: 185 g / eq), and 2 parts of biphenyl type epoxy resin (Nippon Kayaku Corporation "NC3100", epoxy equivalent: 258 g / eq) were dissolved in the mixture. Alumina 1 (270 parts), polymer compound 1 (50% by mass of solid content, number average molecular weight 5500) 26 parts, solid naphthol curing agent ("SN485" manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd., hydroxyl equivalent 215 g / eq, used as 50% solid content methyl ethyl ketone solution) 2 parts, curing accelerator (2-phenyl-1-benzyl-1H-imidazole (1B2PZ), 10% solid content MEK solution) 1 part, methyl ethyl ketone 15 parts were mixed with 10 parts of methyl ethyl ketone, and uniformly dispersed with a high-speed rotary mixer to prepare resin varnish 7. In addition, except that the resin varnish 1 in Example 1 was changed to resin varnish 7, the other operations were carried out in the same manner as in Example 1 to obtain resin sheet 7.
[0312] <Comparative Example 3>
[0313] 6 parts of aminophenol type epoxy resin (Mitsubishi Chemical Corporation "630", epoxy equivalent: 95 g / eq), 5 parts of liquid epoxy resin (Nippon Steel & Sumitomo Metal Chemical Corporation "ZX1059", a 1:1 mixture (mass ratio) of bisphenol A type epoxy resin and bisphenol F type epoxy resin, epoxy equivalent: 169 g / eq), 2 parts of biphenyl type epoxy resin (Mitsubishi Chemical Corporation "YX4000H", epoxy equivalent: 185 g / eq), and 2 parts of biphenyl type epoxy resin (Nippon Kayaku Corporation "NC3100", epoxy equivalent: 258 g / eq) were dissolved in the mixture. Alumina 3 (270 parts), polymer compound 1 (50% by mass of solid content, number average molecular weight 5500) 24 parts, solid naphthol curing agent ("SN485" manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd., hydroxyl equivalent 215 g / eq, used as 50% solid content methyl ethyl ketone solution) 6 parts, curing accelerator (2-phenyl-1-benzyl-1H-imidazole (1B2PZ), 10% solid content MEK solution) 1 part, methyl ethyl ketone 15 parts were mixed with 10 parts of methyl ethyl ketone, and uniformly dispersed with a high-speed rotary mixer to prepare resin varnish 8. In addition, except that the resin varnish 1 in Example 1 was changed to resin varnish 8, the same operation as in Example 1 was performed to obtain a resin sheet 8.
[0314] <Comparative Example 4>
[0315] 6 parts of aminophenol type epoxy resin (Mitsubishi Chemical Corporation "630", epoxy equivalent: 95 g / eq), 5 parts of liquid epoxy resin (Nippon Steel & Sumitomo Metal Chemical Corporation "ZX1059", a 1:1 mixture (mass ratio) of bisphenol A type epoxy resin and bisphenol F type epoxy resin, epoxy equivalent: 169 g / eq), 2 parts of biphenyl type epoxy resin (Mitsubishi Chemical Corporation "YX4000H", epoxy equivalent: 185 g / eq), and 2 parts of biphenyl type epoxy resin (Nippon Kayaku Corporation "NC3100", epoxy equivalent: 258 g / eq) were dissolved in the mixture. Alumina 4 (270 parts), polymer compound 1 (50% by mass of solid content, number average molecular weight 5500) 24 parts, solid naphthol curing agent ("SN485" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., hydroxyl equivalent 215 g / eq, used as 50% solid content methyl ethyl ketone solution) 6 parts, curing accelerator (2-phenyl-1-benzyl-1H-imidazole (1B2PZ), 10% solid content MEK solution) 1 part, methyl ethyl ketone 15 parts were mixed with 10 parts of methyl ethyl ketone, and uniformly dispersed with a high-speed rotary mixer to prepare resin varnish 9. In addition, except that the resin varnish 1 in Example 1 was changed to resin varnish 9, the same operation as in Example 1 was performed to obtain a resin sheet 9.
[0316] The records in the following table are as follows;
[0317] Content of component (A): Content when the non-volatile matter of the resin component excluding component (C) is 100% by mass
[0318] Content of component (C): Content when the non-volatile component of the resin composition is 100% by mass
[0319] [Table 1]
[0320] (Table 1)
[0321]
[0322] *Non-volatile components conversion
[0323] As shown in Examples 1 to 5, it is known that the peel strength of the insulating layer formed by the resin composition containing the components (A) to (D) is excellent. On the other hand, it is known that the peel strength of Comparative Examples 1 to 4 not containing the component (D) is inferior to that of Examples 1 to 5. In addition, it is known that Comparative Examples 3 to 4 in which the component (C) is not treated with N-phenyl-3-aminoalkyltrimethoxysilane have poor lamination properties and poor peel strength due to high melt viscosity.
[0324] In addition, in Examples 1 to 5, when the (E) component and the (F) component were not contained, it was confirmed that the same results as those of the above-mentioned Examples were obtained although there were differences in degree.
[0325] [Explanation of symbols]
[0326] 100 Semiconductor chip packaging
[0327] 110 Semiconductor Chip
[0328] 120 Sealing layer
[0329] 130 Rewiring formation layer (insulating layer)
[0330] 140 Conductor layer (rewiring layer)
[0331] 150 Solder resist layer
[0332] 160 Bumps.
Claims
1. A resin composition comprising: (A) a polymer compound having one or more structures selected from the group consisting of a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyalkylene structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, and a polycarbonate structure in the molecule, (B) Epoxy resin, (C) thermally conductive fillers, and (D) an active ester curing agent, (C) component contains aluminum oxide, The aluminum oxide in the component (C) was surface treated with N-phenyl-3-aminoalkyltrimethoxysilane. The number average molecular weight of the component (A) is 1,000 or more and 1,000,000 or less, When the resin component is 100 mass %, content of the component (A) is 10 mass % or more and 65 mass % or less.
2. The resin composition according to claim 1, wherein The peel strength between a cured product obtained by thermally curing the resin composition at 180° C. for 30 minutes and further thermally curing at 180° C. for 60 minutes and a metal layer formed by plating is 0.4 kgf / cm or more.
3. The resin composition according to claim 1, wherein The peel strength between a cured product obtained by thermally curing the resin composition at 180° C. for 30 minutes and further thermally curing at 180° C. for 60 minutes and a metal layer formed by plating was 0.45 kgf / cm or more.
4. The resin composition according to claim 1, wherein The peel strength between a cured product obtained by thermally curing the resin composition at 180° C. for 30 minutes and further thermally curing at 180° C. for 60 minutes and a metal layer formed by plating is 0.5 kgf / cm or more.
5. The resin composition according to claim 1, wherein The peel strength between a cured product obtained by thermally curing the resin composition at 180° C. for 30 minutes and further thermally curing at 180° C. for 60 minutes and a metal layer formed by plating was 1.5 kgf / cm or less.
6. The resin composition according to claim 1, wherein The peel strength between a cured product obtained by thermally curing the resin composition at 180° C. for 30 minutes and further thermally curing at 180° C. for 60 minutes and a metal layer formed by plating was 1 kgf / cm or less.
7. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (C) is 85% by mass or more.
8. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100 mass %, content of the (C) component is 88 mass % or more.
9. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100 mass %, content of the (C) component is 89 mass % or more.
10. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (C) is 90% by mass or more.
11. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (C) is 95% by mass or less.
12. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100 mass %, the content of the component (C) is 93 mass % or less.
13. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100 mass %, the content of the component (C) is 92 mass % or less.
14. The resin composition according to claim 1, wherein The N-phenyl-3-aminoalkyltrimethoxysilane is selected from N-phenyl-3-aminopropyltrimethoxysilane, and N-phenyl-3-aminooctyltrimethoxysilane.
15. The resin composition according to claim 1, wherein The thermal conductivity of a cured product obtained by thermally curing the resin composition at 180° C. for 90 minutes is 1.5 W / m·K or more and 5.0 W / m·K or less.
16. The resin composition according to claim 1, wherein The thermal conductivity of a cured product obtained by thermally curing the resin composition at 180° C. for 90 minutes is 1.8 W / m·K or more.
17. The resin composition according to claim 1, wherein The thermal conductivity of a cured product obtained by thermally curing the resin composition at 180° C. for 90 minutes is 2.0 W / m·K or more.
18. The resin composition according to claim 1, wherein The thermal conductivity of a cured product obtained by thermally curing the resin composition at 180° C. for 90 minutes was 4.0 W / m·K or less.
19. The resin composition according to claim 1, wherein The thermal conductivity of a cured product obtained by thermally curing the resin composition at 180° C. for 90 minutes was 3.5 W / m·K or less.
20. The resin composition according to claim 1, wherein The component (A) is one or more selected from the group consisting of a resin having a glass transition temperature of 25°C or lower and a resin that is liquid at 25°C.
21. The resin composition according to claim 1, wherein The component (A) has a functional group that can react with the component (B).
22. The resin composition according to claim 1, wherein (A) Component has one or more functional groups selected from the group consisting of a hydroxyl group, an acid anhydride group, a phenolic hydroxyl group, an epoxy group, an isocyanate group, and a urethane group.
23. The resin composition according to claim 1, wherein The component (A) has an imide structure.
24. The resin composition according to claim 1, wherein (A) Component has a phenolic hydroxyl group.
25. The resin composition according to claim 1, wherein The component (A) has a polybutadiene structure and has a phenolic hydroxyl group.
26. The resin composition according to claim 1, wherein The component (A) is a polymer compound having one or more structures selected from the group consisting of a polybutadiene structure, a polyisoprene structure, and a polycarbonate structure in the molecule.
27. The resin composition according to claim 1, wherein The number average molecular weight of the component (A) is 5,000 or more.
28. The resin composition according to claim 1, wherein The number average molecular weight of the component (A) is 900,000 or less.
29. The resin composition according to claim 1, wherein When the resin component is 100% by mass, the content of the component (A) is 60% by mass or less.
30. The resin composition according to claim 1, wherein When the resin component is 100% by mass, the content of the component (A) is 55% by mass or less.
31. The resin composition according to claim 1, wherein When the resin component is 100 mass %, content of the component (A) is 50 mass % or less.
32. The resin composition according to claim 1, wherein When the resin component is 100% by mass, the content of the component (A) is 15% by mass or more.
33. The resin composition according to claim 1, wherein When the resin component is 100% by mass, the content of the component (A) is 20% by mass or more.
34. The resin composition according to claim 1, wherein When the resin component is 100 mass %, content of the component (A) is 25 mass % or more.
35. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (B) is 1% by mass or more.
36. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (B) is 2% by mass or more.
37. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (B) is 3% by mass or more.
38. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (B) is 10% by mass or less.
39. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (B) is 8% by mass or less.
40. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (B) is 6% by mass or less.
41. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100 mass %, content of the component (D) is 5 mass % or less.
42. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100 mass %, the content of the component (D) is 3 mass % or less.
43. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (D) is 2% by mass or less.
44. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100 mass %, the content of the component (D) is 0.1 mass % or more.
45. The resin composition according to claim 1, wherein When the nonvolatile matter in the resin composition is 100 mass %, content of the component (D) is 0.5 mass % or more. The resin composition according to claim 1 , which is a resin composition for an insulating layer of a semiconductor chip package.
47. The resin composition according to claim 1, which is a resin composition for an insulating layer of a circuit substrate in which a circuit is formed by a semi-additive process.
48. A resin sheet comprising a support and a resin composition layer provided on the support and comprising the resin composition according to any one of claims 1 to 47.
49. A circuit board comprising an insulating layer formed from a cured product of the resin composition according to any one of claims 1 to 47.
50. A semiconductor chip package comprising the circuit substrate according to claim 49, and a semiconductor chip mounted on the circuit substrate. 51 . A semiconductor chip package comprising a semiconductor chip sealed with the resin composition according to claim 1 or the resin sheet according to claim 48 .
Citation Information
Patent Citations
Epoxy resin composition, and sheet, preperg-like material, sheet with metal foil, laminated sheet, electrical insulating material and resist material obtained therefrom
JP2004277460A
Thermosetting resin composition containing modified polyimide resin
JP2006037083A
Thermosetting resin composition, cured product of the same, active ester resin, semiconductor sealing material, prepreg, circuit board, and build-up film
JP2013040270A
Resin composition for interlayer insulation of multilayer printed wiring board
WO2008153208A1
Resin composition for printed wiring board
WO2010053185A1